Toner

By using characteristic toner particles, the energy storage elastic modulus and temperature change rate are controlled, the problems of low-temperature fixability and uneven concentration in high-speed image forming equipment are solved, and efficient image formation effect is achieved.

CN112506012BActive Publication Date: 2025-03-04CANON KK
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202010952596.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-09-13
Filing Date
2020-09-11
Publication Date
2025-03-04
Estimated Expiration
2040-09-11

AI Technical Summary

Technical Problem

It is difficult for the conventional toner to achieve both low temperature fixability and uneven solid image density in high-speed image forming equipment.

Method used

By using toner particles containing binder resin, the rate of change of energy storage elastic modulus and temperature to energy storage elastic modulus is controlled, so as to ensure that the toner has good low-temperature fixability in high-speed equipment and suppresses uneven concentration.

Benefits of technology

It realizes good low-temperature fixability in high-speed equipment, effectively suppresses uneven concentration of solid images, and improves the durability and storage stability of toner.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0002677511410000101
    Figure BDA0002677511410000101
  • Figure BDA0002677511410000111
    Figure BDA0002677511410000111
  • Figure BDA0002677511410000361
    Figure BDA0002677511410000361
Patent Text Reader

Abstract

The present invention relates to a toner. The toner includes toner particles containing a binder resin, wherein in a temperature T (°C)-storage elastic modulus G' (Pa) curve obtained by measuring the toner with a rheometer, the storage elastic modulus G' (80°C) at 80°C is 2.0×10 3 Pa to 2.0×10 5 Pa, and the minimum value of the change in storage elastic modulus G' with respect to temperature T (dG' / dT) in the range of 60℃ to 80℃ is ‑1.0×10 6 Below, and when the temperature of the toner increases, where the projected area of ​​the toner at 80°C is S1 (μm 2 ), the radius of the projected area of ​​the toner at 80°C is R1 (μm), and the radius of the projected area of ​​the toner at 120°C is S2 (μm 2 ), S1, R1 and S2 satisfy the following formula (1): (1) S2 / S1×1 / R1≤0.22.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a toner used in an image forming method for developing an electrophotographic image or an electrostatic charge image. Background Art

[0002] Image forming equipment using electrophotography has high requirements for energy saving, therefore, the low temperature fixability of toner needs to be improved. Generally, low temperature fixability depends on the viscosity of the toner, and a toner whose viscosity is rapidly reduced under the action of heat during fixing is required. However, a toner that satisfies this low temperature fixability is unlikely to withstand external stress caused by agitation in the developing device and temperature rise of the main body, and problems such as reduction in durability and reduction in storage stability caused by embedding of external additives are likely to occur.

[0003] Furthermore, in recent years, in addition to energy saving, there is a strong demand for high-speed processing equipment. In a high-speed image forming apparatus in which a solid image is output over the entire surface, the unevenness on the paper surface causes problems such as uneven density to produce a difference in toner melting degree. This phenomenon may occur in a toner having a low viscosity, and due to technical obstacles, it is extremely difficult to achieve both energy saving and high-speed processing at the same time.

[0004] Japanese Patent Application Publication No. 2014-167602 describes a toner in which the storage elastic modulus G' at a temperature of 80° C. to 140° C. is controlled in order to improve low-temperature fixability and offset resistance. Summary of the invention

[0005] However, it has been found that although the toner whose storage elastic modulus G' is controlled as in the above document exhibits a certain effect on the low temperature fixability of the toner, it causes solid image density unevenness in a high-speed image forming apparatus. Therefore, there is room for improvement in solid image density unevenness.

[0006] The present invention provides a toner which solves the above-mentioned problems.

[0007] That is, to provide a toner which has satisfactory low-temperature fixability even in a high-speed device and can suppress unevenness in solid image density.

[0008] As a result of repeated studies, the present inventors have found that the above-mentioned requirements can be satisfied by using the following configuration, and have completed the present invention.

[0009] That is, the present invention relates to a toner comprising toner particles containing a binder resin, wherein

[0010] In the temperature T (° C.)-storage elastic modulus G' (Pa) curve obtained by measuring the toner at a temperature increase rate of 2.0° C. / min using a flat plate rotational rheometer,

[0011] (i) Storage elastic modulus G'(80℃) at 80℃ is 2.0×10 3 Pa to 2.0×10 5 Pa; and

[0012] (ii) The minimum value of the change in storage elastic modulus G' with respect to temperature T (dG' / dT) in the range of 60°C to 80°C is -1.0×10 6 Below, and

[0013] When the temperature of the toner is increased from 25°C to 120°C at a heating rate of 10°C / min, the projected area of ​​the toner at 80°C is S1 (μm 2 ), the radius of the projected area of ​​the toner at 80°C is R1 (μm), and the radius of the projected area of ​​the toner at 120°C is S2 (μm 2 )hour,

[0014] S1, R1 and S2 satisfy the following formula (1):

[0015] (1)S2 / S1×1 / R1≤0.22.

[0016] The present invention can provide a toner which has satisfactory low-temperature fixability even in a high-speed device and can suppress unevenness in solid image density.

[0017] Further features of the present invention will become apparent from the following description of exemplary embodiments. DETAILED DESCRIPTION

[0018] Unless otherwise specified, the description "from XX to YY" or "XX to YY" expressing a numerical range means that the numerical range includes the lower limit and the upper limit as endpoints.

[0019] When a numerical range is described in sections, the upper limit and the lower limit of each numerical range can be arbitrarily combined.

[0020] In order to improve the low temperature fixability, it is necessary to make the toner melt rapidly in a very short time when it passes through the fixing roller gap. Generally, as a method for making the toner melt rapidly, it is known to control the melting characteristics of the resin component in the toner. In recent years, various methods of controlling the melting characteristics of the resin component by plasticization have been studied using fixing aids (additives such as low melting point waxes and crystalline resins).

[0021] Therefore, in the case of evaluating the toner to which the crystalline polyester is added from the viewpoint of improving the low-temperature fixing property, it was found that although a certain effect was produced on the low-temperature fixing property, solid image density unevenness was produced under the high-speed printing conditions assumed by the next-generation technology. Therefore, in order to meet the future demand for energy saving and high speed, even if the viscosity of the toner is reduced when the toner passes through the fixing roller nip, the toner does not wet spread too much at the convex part of the paper, and research is required to make it possible to suppress the solid image density unevenness.

[0022] As a result of studies conducted to solve the trade-off problem between improvement of low-temperature fixability and suppression of solid image density unevenness, the present inventors came up with the idea that the above-mentioned problem can be solved by using a toner having the following characteristics.

[0023] That is, the present invention relates to a toner comprising toner particles containing a binder resin, wherein

[0024] In the temperature T (° C.)-storage elastic modulus G' (Pa) curve obtained by measuring the toner at a temperature increase rate of 2.0° C. / min using a flat plate rotational rheometer,

[0025] (i) Storage elastic modulus G'(80℃) at 80℃ is 2.0×10 3 Pa to 2.0×10 5 Pa; and

[0026] (ii) The minimum value of the change in storage elastic modulus G' with respect to temperature T (dG' / dT) in the range of 60°C to 80°C is -1.0×10 6 Below, and

[0027] When the temperature of the toner is increased from 25°C to 120°C at a heating rate of 10°C / min, the projected area of ​​the toner at 80°C is S1 (μm 2 ), the radius of the projected area of ​​the toner at 80°C is R1 (μm), and the radius of the projected area of ​​the toner at 120°C is S2 (μm 2 )hour,

[0028] S1, R1 and S2 satisfy the following formula (1):

[0029] (1)S2 / S1×1 / R1≤0.22.

[0030] The toner will be described in detail below.

[0031] In the temperature T (°C)-storage elastic modulus G' (Pa) curve obtained by measuring the toner at a temperature increase rate of 2.0°C / min using a flat plate rotational rheometer, the storage elastic modulus G' (80°C) at 80°C needs to be 2.0×103 Pa to 2.0×10 5 Pa.

[0032] In addition, the storage elastic modulus G' (80°C) is preferably 2.0×10 3 Pa to 1.5×10 5 Pa, and more preferably 2.0×10 3 Pa to 1.0×10 5 Pa, because satisfactory low-temperature fixability can be obtained.

[0033] Generally, there are numerous concavoconvexities on the surface of paper, and when passing through the fixing nip, the concave portions tend to receive less heat and pressure than the convex portions. Therefore, the toner in the concave portions may not be sufficiently melted compared to the toner in the convex portions, and fixing defects may occur. As a result of intensive studies, the present inventors have found that the storage elastic modulus G'(80°C) of the toner at 80°C corresponds to the melting degree of the toner in the concave portions on the paper.

[0034] The storage elastic modulus G' is an index indicating the elasticity of a polymer, that is, the reversibility to stress. The storage elastic modulus G' of a toner indicates the force of restoring the original state when the toner is deformed by heat and pressure in the fixing roller nip portion. That is, the storage elastic modulus indicates whether the molecules forming the toner have a spring-like property, and the smaller the modulus value, the softer the toner is and the better the low-temperature fixing property is.

[0035] When the storage elastic modulus G' (80°C) of the toner is greater than 2.0×10 5 Pa, the toner viscosity cannot be sufficiently reduced by the heat received in the fixing nip and the residual heat received after passing through the fixing nip. As a result, the adhesion between the medium and the toner and between the toner particles is reduced, and when the fixed image is rubbed, fixing defects such as toner peeling off from the medium surface occur.

[0036] In addition, when outputting images under high-speed printing conditions, fixing defects such as partial loss or loss of print also occur when the medium passes through the fixing nip. This is believed to be because the time required for the toner on the medium to pass through the fixing nip is reduced due to the speed increase of the machine.

[0037] Toner that is not sufficiently melted while passing through the fixing nip firmly adheres to the fixing member side as a heat source and smears the printed portion. Since the printed portion is missing or defective at the moment the toner passes through the fixing nip, the presence or absence of such a defect is determined only by the heat received by the toner in the fixing nip. In other words, there is no influence caused by the melting of the toner caused by the residual heat after passing through the fixing nip.

[0038] As a result of intensive studies to prevent partial loss or chipping of print, the present inventors have come up with the idea that the above-mentioned problems can be solved by adopting the following features.

[0039] In the temperature T (°C)-storage elastic modulus G' (Pa) curve obtained by measuring the toner at a temperature increase rate of 2.0°C / min using a flat plate rotational rheometer, the minimum value of the change in storage elastic modulus G' with respect to temperature T (dG' / dT) in the range of 60°C to 80°C is -1.0×10 6 the following.

[0040] From the viewpoint of obtaining satisfactory low-temperature fixability, the minimum value of the change amount (dG' / dT) is preferably -5.0×10 6 The lower limit is not particularly limited, but is preferably -1.0×10 8 More preferably -5.0×10 7 above.

[0041] The variation (dG' / dT) indicates the slope of the storage elastic modulus G' with respect to the temperature T. In other words, a smaller value of the variation means that the toner viscosity is likely to change faster, and it can be said that defect or loss of a printed portion of the toner is more likely to be suppressed.

[0042] The minimum value of the change in storage elastic modulus G' relative to temperature T (dG' / dT) is greater than -1.0×10 6 In such a case, the viscosity cannot be sufficiently reduced in the short time that the toner passes through the fixing nip, and the printed portion is chipped or missing.

[0043] The storage elastic modulus G' (80°C) of the toner and the minimum value of the change in the storage elastic modulus G' of the toner with respect to the temperature T (dG' / dT) can be controlled, for example, by changing the composition of the resin component in the toner or the composition of the fixing aid and by changing the dispersibility of the materials (fixing aid and colorant, etc.). In addition, the control can also be performed by adjusting the amount of inorganic particles contained in the toner.

[0044] In addition, in the temperature T (°C)-storage elastic modulus G' (Pa) curve, the storage elastic modulus G' (120°C) at 120°C is preferably 2.0×10 3 Pa to 2.0×10 4 Pa, and more preferably 4.0×10 3 Pa to 1.0×10 4 Pa.

[0045] As described above, the convex portions of the paper surface tend to receive more heat when passing through the fixing nip than the concave portions. Therefore, the toner on the convex portions may be excessively melted compared to the toner in the concave portions, and solid image density unevenness may occur. As a result of intensive studies, the present inventors have found that the storage elastic modulus G'(120°C) of the toner at 120°C corresponds to the degree of melting at the convex portions on the paper.

[0046] By setting the storage elastic modulus G' (120°C) of the toner within the above range, it is possible to suppress the non-uniformity of the solid image density and obtain a toner having satisfactory heat offset resistance. The storage elastic modulus G' (120°C) can be controlled, for example, by changing the composition of the resin component or the composition of the fixing aid in the toner and by changing the dispersibility of the materials (fixing aid and colorant, etc.). In addition, the control can also be performed by adjusting the amount of inorganic particles contained in the toner.

[0047] When the temperature of the toner is increased from 25°C to 120°C at a heating rate of 10°C / min, the projected area of ​​the toner at 80°C is S1 (μm 2 ), the radius of the projected area of ​​the toner at 80°C is R1 (μm), and the radius of the projected area of ​​the toner at 120°C is S2 (μm 2 )hour,

[0048] S1, R1 and S2 satisfy the following formula (1).

[0049] (1)S2 / S1×1 / R1≤0.22.

[0050] By setting the relationship between S1, S2, and R1 within the above range, solid image density unevenness can be suppressed even during high-speed printing. The reason for this is considered to be as follows.

[0051] As described above, it is considered that the main cause of the uneven density of the solid image is the uneven melting of the toner due to the unevenness of the medium. In particular, in the case of commonly used paper, there is a deviation of about 30 μm between the concave and convex parts of the paper surface.

[0052] Generally, the temperature of the fixing device is set so that the toner in the concave portion receiving less heat in the fixing nip portion can be fixed, and the toner on the convex portion receives excessive heat in the fixing nip portion. It has been found that in the case of a machine adapted to high speed, the difference in the amount of heat received by the toner in the concave portion and the toner on the convex portion becomes larger, and there is a difference of about 40°C in the reaching temperature of the toner.

[0053] Therefore, in order to suppress the uneven density of solid images even in machines adapted to high speed, it is required that the difference in the wet spreading area of ​​the toner on the paper is small even under different temperature conditions. As a result of intensive research conducted to obtain such an effect, the present inventors have found that it is important to set the wet spreading parameter calculated by formula (1) within the above range.

[0054] The ease with which the toner wet spreads on the medium can be controlled by a combination of the toner material and the toner particle size. However, the toner particle size is generally limited by the construction of the body and the cartridge CRG and cannot be freely selected in some cases. Therefore, attention is focused on controlling the ease with which the toner wet spreads on the medium by a combination of the toner material.

[0055] Specifically, it was decided to adopt the product of 1 / R1 in order to remove the factor of the toner particle size from the ease with which the toner wet spreads on the medium. The reason for this is described below.

[0056] Assuming that the toner is spherical, the volume of the toner before fixing is proportional to the cube of the radius. At the same time, the projected area of ​​the toner on the medium is proportional to the square of the radius. Assuming that the toner is wet spread to a certain thickness on the medium, the difference between the volume index and the area index needs to be considered.

[0057] Therefore, it is considered that the factor of the toner particle size can be removed by taking the product of 1 / R1 and the rate of change S2 / S1 of the projected area at 80°C and the projected area at 120°C.

[0058] In the case where S2 / S1×1 / R1 is greater than 0.22, the area variation of the toner on the convex portion relative to the concave portion on the paper surface becomes large, resulting in uneven density of the solid image. S2 / S1×1 / R1 is preferably 0.20 or less. Meanwhile, the lower limit is not particularly limited, but it is preferably 0.12 or more, and more preferably 0.15 or more.

[0059] The value of S2 / S1×1 / R1 can be controlled, for example, by using a binder resin described later. This control can also be adjusted by adjusting the dispersion diameter of the crystalline material (crystalline resin and wax, etc.), the melting point of the crystalline material, and the compatibility of the crystalline material and the binder resin.

[0060] In the case where the amount of ethyl acetate-insoluble matter of the toner when the toner is extracted by Soxhlet extraction using ethyl acetate for 18 hours is α (mass %), α is preferably 25.0 mass % to 55.0 mass %, and more preferably 30.0 mass % to 50.0 mass %.

[0061] Since ethyl acetate has an ester group and has high polarity, a linear component also having an ester group and high polarity can be extracted. Meanwhile, in the case where the molecules are strongly entangled with each other even if the component has high polarity, or in the case of a non-polar component, extraction is difficult. That is, the cross-linked structure between the vinyl polymer part and the non-crystalline polyester part described below and the cross-linked structure in the non-crystalline polyester part, etc. are substances that are insoluble in ethyl acetate.

[0062] The linear component soluble in ethyl acetate plasticizes the resin in a high temperature and high humidity environment, so when the amount of ethyl acetate insoluble matter in the binder resin satisfies the above range, when the toner is used for a long time in a high temperature and high humidity environment, the plasticization of the toner is suppressed and the durability is improved.

[0063] The amount of the ethyl acetate insoluble matter can be adjusted by changing the monomer composition and production conditions of the binder resin and the toner production conditions.

[0064] When the amount of tetrahydrofuran-insoluble matter of the toner when the toner is extracted by Soxhlet extraction using tetrahydrofuran (THF) for 18 hours is β (mass %), β preferably satisfies the following formula (2), more preferably satisfies the following formula (2′), and even more preferably satisfies the following formula (2″).

[0065] (2)5.0≤β≤30.0

[0066] (2')5.0≤β≤20.0

[0067] (2”)8.0≤β≤20.0.

[0068] Since THF has a furan ring and can elute not only polar linear components but also polar entangled components, can elute even non-polar linear components, and can elute most of the binder resin components.

[0069] That is, the cross-linked structure in the non-crystalline polyester part described later becomes a THF insoluble substance. The THF insoluble substance is difficult to deform in the temperature range during fixing, excessive deformation of the toner when the toner is melted can be suppressed, and the unevenness of the solid image density can be suppressed. In addition, since the external additive can be prevented from being embedded in the toner, the durability is improved.

[0070] The amount of the THF-insoluble matter can be adjusted by changing the monomer composition and production conditions of the binder resin and the toner production conditions.

[0071] Furthermore, the amount α (mass %) of the ethyl acetate insoluble matter and the amount β (mass %) of the tetrahydrofuran insoluble matter preferably satisfy the following formula (3), more preferably satisfy the following formula (3'), and even more preferably satisfy the following formula (3").

[0072] (3) 10.0 ≤ (α-β) ≤ 40.0

[0073] (3')15.0≤(α-β)≤33.0

[0074] (3")17.0≤(α-β)≤25.0.

[0075] As described above, the amount of ethyl acetate insoluble matter is affected by, for example, the crosslinking structure between the vinyl polymer part and the non-crystalline polyester part and the crosslinking structure in the non-crystalline polyester part. In addition, the amount of THF insoluble matter is affected by the crosslinking structure in the non-crystalline polyester part. That is, (α-β) in formula (3) is affected by the crosslinking structure between the vinyl polymer part and the non-crystalline polyester part.

[0076] As described below, the cross-linking structure between the vinyl polymer part and the non-crystalline polyester part has a short distance between the cross-linking points and forms a dense network, so that entanglement with other raw materials and material dispersibility in the toner can be improved. As a result, in the case of a toner in which (α-β) satisfies the above range, solid image density unevenness and fogging can be suppressed.

[0077] It is preferred that the toner contains tetrahydrofuran-insoluble matter when the toner is extracted for 18 hours by using tetrahydrofuran Soxhlet extraction. In addition, the storage elastic modulus G'(120°C) at 120°C measured by measuring the tetrahydrofuran-insoluble matter at a heating rate of 2.0°C / min using a flat plate rotational rheometer is preferably 1.0×10 5 Pa to 1.0×10 7 Pa, and more preferably 2.0×10 5 Pa to 5.0×10 6 Pa.

[0078] When the storage elastic modulus G′ (120° C.) of the THF-insoluble matter satisfies the above range, solid image density unevenness can be suppressed and a toner having satisfactory durability can be obtained.

[0079] Binder resin

[0080] The binder resin is not particularly limited, and known resins can be used. The binder resin preferably contains a hybrid resin having a vinyl polymer part and a non-crystalline polyester part. In the case where the binder resin contains a hybrid resin having a non-crystalline polyester part with excellent melting properties and a vinyl polymer part with excellent charging characteristics and a high softening point, while the softening point of the binder resin is improved, excellent charging stability and low-temperature fixing properties are achieved. As a result, low-temperature fixing properties and stability of image density under high humidity environments are further improved.

[0081] The amount of the hybrid resin in the binder resin is preferably 50% by mass to 100% by mass, more preferably 80% by mass to 100% by mass, and even more preferably 90% by mass to 100% by mass.

[0082] In the hybrid resin, the vinyl polymer part and the non-crystalline polyester part are preferably hybridized by transesterification. As a result, a crosslinked structure is formed between the vinyl polymer part and the non-crystalline polyester part, and it becomes easy to control the amount α (mass %) of ethyl acetate insoluble matter and the amount β (mass %) of THF insoluble matter.

[0083] The crosslinked structure between the vinyl polymer part and the non-crystalline polyester part has a short distance between crosslinked points and can form a relatively small network, so that the storage elastic modulus G' of the crosslinked part can be improved. Therefore, the solid image density unevenness can be suppressed.

[0084] In the hybrid resin, the mass ratio of the non-crystalline polyester site to the vinyl polymer site (non-crystalline polyester site:vinyl polymer site) is preferably 50:50 to 98:2, more preferably 70:30 to 97:3, and even more preferably 90:10 to 97:3.

[0085] That is, the amount of the non-crystalline polyester site in the hybrid resin is preferably 50% by mass to 98% by mass, more preferably 70% by mass to 97% by mass, and even more preferably 90% by mass to 97% by mass.

[0086] By setting the above range, while achieving the advantages of the hybrid resin, stable low-temperature fixability is exhibited regardless of the environment. In addition, the amount α (mass %) of ethyl acetate insoluble matter and the amount β (mass %) of THF insoluble matter can be easily controlled, and solid image density unevenness can be suppressed.

[0087] As monomers constituting the polyester resin or the polyester moiety, the following compounds may be mentioned.

[0088] The alcohol component may exemplify the following diols:

[0089] Ethylene glycol, propylene glycol, 1,3-butanediol, 1,4-butanediol, 2,3-butanediol, diethylene glycol, triethylene glycol, 1,5-pentanediol, 1,6-hexanediol, neopentyl glycol, 2-ethyl-1,3-hexanediol, hydrogenated bisphenol A, bisphenols given by the following formula (I) and derivatives thereof, and diols given by the following formula (II).

[0090]

[0091] (In the formula, R represents an ethylene group or a propylene group; x and y are each an integer of 0 or more; and the average value of x+y is 0 or more and 10 or less.)

[0092]

[0093] (In the formula, R' is -CH2CH2-, x' and y' are each an integer greater than 0; and the average value of x'+y' is 0 to 10. )

[0094] The following dicarboxylic acids are examples of the acid component:

[0095] benzenedicarboxylic acids and their anhydrides, for example, phthalic acid, terephthalic acid, isophthalic acid and phthalic anhydride; alkyl dicarboxylic acids, for example, succinic acid, adipic acid, sebacic acid and azelaic acid, and their anhydrides; succinic acid substituted by an alkyl group having 6 to 18 carbons or by an alkenyl group having 6 to 18 carbons, and its anhydrides; and unsaturated dicarboxylic acids, for example, fumaric acid, maleic acid, citraconic acid and itaconic acid, and their anhydrides.

[0096] The polyester resin or polyester part preferably includes a monomer unit derived from a polyol or a monomer unit derived from a polycarboxylic acid. That is, the non-crystalline polyester part preferably has a cross-linked structure with at least one selected from the group consisting of a trivalent or higher polyol and a trivalent or higher polycarboxylic acid. As a result, a cross-linked structure is formed in the non-crystalline polyester part, and it becomes easy to control the amount β (mass %) of THF-insoluble matter.

[0097] The cross-linked structure has a long distance between cross-linked points and can easily form a relatively large network, so that a three-dimensional network structure can be constructed throughout the binder resin. Therefore, solid image density unevenness and durable stability of the toner are improved.

[0098] The trivalent or higher polycarboxylic acid can be exemplified by 1,2,4-benzenetricarboxylic acid (trimellitic acid), 1,2,4-cyclohexanetricarboxylic acid, 1,2,4-naphthalenetricarboxylic acid and pyromellitic acid, and anhydrides and lower alkyl esters thereof.

[0099] Among the above, aromatic compounds which are stable also to environmental changes are preferred, for example, 1,2,4-benzenetricarboxylic acid and its anhydride.

[0100] The trivalent or higher polyol can be exemplified by 1,2,3-propanetriol, trimethylolpropane, hexanetriol, and pentaerythritol.

[0101] The binder resin preferably includes a resin composition comprising a hybrid resin having a vinyl polymer site and a non-crystalline polyester site, and more preferably a resin composition comprising a hybrid resin having a vinyl polymer site and a non-crystalline polyester site.

[0102] The resin composition preferably comprises

[0103] (i) at least one of a structure in which a long-chain alkyl monohydric alcohol having an average terminal carbon number of 27 to 50 at the non-crystalline polyester portion is condensed and a structure in which a long-chain alkyl monocarboxylic acid having an average terminal carbon number of 27 to 50 at the non-crystalline polyester portion is condensed, and

[0104] (ii) Aliphatic hydrocarbons having an average carbon number of 27 to 50.

[0105] In the case where the binder resin includes the above-mentioned resin composition, when a crystalline polyester is added, the crystallization rate of the crystalline polyester is improved, and a toner having good heat-resistant storage stability can be obtained.

[0106] The amount of the resin composition in the binder resin is preferably 50% by mass to 100% by mass, more preferably 80% by mass to 100% by mass, and even more preferably 90% by mass to 100% by mass.

[0107] The structure in which a long-chain alkyl monoalcohol is condensed is also referred to as an alcohol residue below. The structure in which a long-chain alkyl monocarboxylic acid is condensed is also referred to as a carboxylic acid residue below. In addition, these residues are also referred to as long-chain alkyl components.

[0108] Here, the polyester resin having at least one of an alcohol residue of a long-chain alkyl monoalcohol and a carboxylic acid residue of a long-chain alkyl monocarboxylic acid as a terminal means a resin into which these long-chain alkyl components are introduced by reaction with a polyester resin as a main binder component.

[0109] Meanwhile, in the case where the resin composition includes an aliphatic hydrocarbon having the above-mentioned average carbon number, for example, when the long-chain alkyl component has been alcohol-modified or acid-modified, the resin composition also includes an unmodified component.

[0110] The resin composition means that it includes a polyester resin into which a long-chain alkyl component is introduced (for example, it is an unmodified product of the long-chain alkyl component) and an aliphatic hydrocarbon component.

[0111] The average value of the carbon numbers of the long-chain alkyl components is determined by the following method.

[0112] The distribution of carbon numbers in the long-chain alkyl component is measured by gas chromatography (GC) as follows. 10 mg of a sample is accurately weighed and introduced into a sample bottle. 10 g of hexane accurately weighed is added to the sample bottle and the lid is closed, followed by heating to a temperature of 150° C. on a hot plate and mixing.

[0113] Thereafter, in a state in which a long-chain alkyl component is not precipitated, the sample is injected into an injection port of a gas chromatograph and analyzed by the following measuring instrument and measuring conditions, thereby obtaining a graph in which the horizontal axis is the carbon number and the vertical axis is the signal intensity.

[0114] Then, using the obtained graph, the percentage of the peak area of ​​the component at each carbon number relative to the total area of ​​all detected peaks is calculated and taken as the percentage occurrence (area %) of each hydrocarbon compound. The carbon number is plotted on the horizontal axis and the hydrocarbon compound occurrence (area %) is plotted on the vertical axis to construct a carbon number distribution graph. The average carbon number refers to the carbon number at the top of the peak in the graph of the carbon number distribution.

[0115] The measuring instruments and measuring conditions are as follows.

[0116] GC: 6890GC from Hewlett-Packard

[0117] Column: ULTRA ALLOY-1P / N:UA1-30m-0.5F (from Frontier Laboratories Ltd.)

[0118] Carrier gas: He

[0119] Column oven: (1) maintain at 100°C for 5 minutes, (2) increase the temperature to 360°C at 30°C / min, (3) maintain at 360°C for 60 minutes

[0120] Inlet: Temperature = 300°C

[0121] Initial pressure: 10.523 psi

[0122] Split ratio: 50:1

[0123] Column flow rate: 1mL / min

[0124] Furthermore, the total content ratio of aliphatic hydrocarbons having an average carbon number of 27 to 50, structures (alcohol residues) in which long-chain alkyl monoalcohols having an average carbon number of 27 to 50 are condensed, and structures (carboxylic acid residues) in which long-chain alkyl monocarboxylic acids having an average carbon number of 27 to 50 are condensed in the resin composition is preferably 2.5% by mass to 10.0% by mass, and more preferably 3.5% by mass to 7.5% by mass.

[0125] By setting the content ratio of the component derived from the long-chain alkyl group within the above range, the crystallization rate of the crystalline polyester can be easily controlled, and a toner having good storage stability can be obtained.

[0126] Furthermore, in a temperature-endothermic amount curve of the resin composition obtained by differential scanning calorimetry (DSC), the peak top temperature of the endothermic peak of the resin composition is preferably 60.0°C to 90.0°C.

[0127] The endothermic amount (ΔH) of the endothermic peak is preferably 0.10 J / g to 1.90 J / g, and more preferably 0.20 J / g to 1.00 J / g.

[0128] In order to achieve both low temperature fixability of the toner and suppression of non-uniformity in solid image density, it is preferred that the crystalline polyester is uniformly dispersed in the toner. For this purpose, it is preferred that the component derived from the long chain alkyl group is uniformly dispersed in the binder resin, and it is preferred that the amount of the component which is not bonded to the polyester resin component and is free, that is, the amount of the unmodified aliphatic hydrocarbon is optimized.

[0129] The endothermic peak of the unmodified aliphatic hydrocarbon appears in the temperature-endothermic curve obtained by differential scanning calorimetry (DSC). When the endothermic value ΔH observed by DSC is within the above range, it means that the amount of free long-chain alkyl component is small, that is, the component is introduced into the polyester resin (main binder).

[0130] Therefore, the present inventors believe that by optimizing the endothermic amount (ΔH) of the endothermic peak, the component derived from the long-chain alkyl group can be easily and uniformly dispersed in the resin composition.

[0131] In the present invention, the peak top temperature and the endothermic amount (ΔH) of the endothermic peak are measured by the following method.

[0132] The peak top temperature and endothermic peak quantity of the endothermic peak by differential scanning calorimetry (DSC) were measured using a "Q2000" differential scanning calorimeter (TA Instruments) based on ASTM D 3418-82. The temperature calibration of the instrument detection part was performed using the melting points of indium and zinc, and the heat of fusion of indium was used to calibrate the heat.

[0133] Specifically, about 5 mg of the measurement sample was accurately weighed and introduced into an aluminum pan and an empty aluminum pan was used as a control in the measurement temperature range between 30°C and 200°C at a temperature increase rate of 10°C / min at normal temperature and humidity. The measurement was performed by initially raising the temperature to 200°C, then cooling to 30°C, and then reheating. The temperature at the peak top of the maximum endothermic peak in the temperature range of 30°C to 200°C in the DSC curve (temperature-endothermic heat curve) obtained during the temperature increase was obtained. In addition, the endothermic heat ΔH of the endothermic peak is the integral value of the endothermic peak.

[0134] The method for controlling the amount of the free long-chain alkyl component, that is, the amount of the endothermic peak in DSC can be exemplified by a method of increasing the alcohol modification rate or the acid modification rate of the aliphatic hydrocarbon.

[0135] Thus, regarding the alcohol- or acid-modified long-chain alkyl component, it reacts with the polyester resin during the polymerization reaction to be inserted into the polyester resin, and as a result, the endothermic peak of the alcohol- or acid-modified long-chain alkyl component does not appear in DSC measurement. On the other hand, the unmodified aliphatic hydrocarbon component does not have a site for reacting with the polyester resin, and therefore, exists in the polyester resin in a free state and increases the endothermic amount in DSC.

[0136] As described above, the long-chain alkyl monohydric alcohol having an average carbon number of 27 to 50 and the long-chain alkyl monocarboxylic acid having an average carbon number of 27 to 50 used in the present invention are obtained by industrially alcohol- or acid-modification of raw material aliphatic hydrocarbons.

[0137] The aliphatic hydrocarbon includes saturated hydrocarbons and unsaturated hydrocarbons and can be exemplified by alkanes, alkenes and alkynes, and cyclic hydrocarbons such as cyclohexane, but saturated hydrocarbons (alkanes) are preferred.

[0138] For example, for alcohol modified products, it is known that aliphatic hydrocarbons having 27 to 50 carbon atoms can be converted into alcohols by liquid phase oxidation of molecular oxygen-containing gas in the presence of a catalyst such as boric acid, boric anhydride or metaboric acid. The amount of catalyst used is preferably 0.01 mol to 0.5 mol relative to 1 mol of the raw material saturated aliphatic hydrocarbon.

[0139] A wide range of molecular oxygen-containing gases can be used for the molecular oxygen-containing gas injected into the reaction system, for example, oxygen, air, or these diluted with an inert gas; however, an oxygen concentration of 3% to 20% is preferred. The reaction temperature is preferably 100°C to 200°C.

[0140] The endothermic amount measured by DSC can be controlled by optimizing the reaction conditions and removing the unmodified aliphatic hydrocarbon component by a purification operation after the modification reaction. The modification rate of the aliphatic hydrocarbon component is preferably 85% or more, and more preferably 90% or more. At the same time, the upper limit is preferably 99% or less.

[0141] In addition, the resin composition preferably includes a structure in which a long-chain alkyl monool having an average value of 27 to 50 carbon numbers at the terminals is condensed, and an aliphatic hydrocarbon having an average value of 27 to 50 carbon numbers. The long-chain alkyl monool preferably includes a secondary alcohol, and more preferably includes a secondary alcohol as a main component. Having a secondary alcohol as a main component means that 50% by mass or more of the long-chain alkyl monool is a secondary alcohol.

[0142] By using a secondary alcohol as the main component of the long-chain alkyl monool, the long-chain alkyl component can easily assume a folded structure. As a result, steric hindrance and the like are suppressed, the long-chain alkyl component can be more uniformly present in the resin composition, and storage stability is further improved.

[0143] The vinyl polymer site contained in the hybrid resin preferably includes monomer units derived from styrene and monomer units derived from acrylate and / or methacrylate, and the total content ratio of monomer units derived from acrylate and methacrylate in all monomer units forming the vinyl polymer site is preferably 50 mol% to 98 mol%, more preferably 70 mol% to 97 mol%, and even more preferably 85 mol% to 97 mol%.

[0144] As a result, the density of the cross-linked structure between the vinyl polymer part and the non-crystalline polyester part can be adjusted, which facilitates the control of the amount α (mass %) of ethyl acetate insoluble matter and the amount β (mass %) of THF insoluble matter. Therefore, the unevenness of the solid image density can be suppressed.

[0145] The following compounds are examples of vinyl monomers used to form the vinyl polymer site:

[0146] Styrene and its derivatives, such as styrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, p-methoxystyrene, p-phenylstyrene, p-chlorostyrene, 3,4-dichlorostyrene, p-ethylstyrene, 2,4-dimethylstyrene, p-butylstyrene, p-tert-butylstyrene, p-hexylstyrene, p-octylstyrene, p-nonylstyrene, p-decylstyrene and p-dodecylstyrene; unsaturated monoolefins, such as ethylene, propylene, butylene and isobutylene; unsaturated polyolefins, such as butadiene and isoprene; vinyl halides, such as vinyl chloride, vinylidene chloride, vinyl bromide and vinyl fluoride; vinyl esters, such as vinyl acetate, vinyl propionate and vinyl benzoate; methacrylates, such as methyl methacrylate, ethyl methacrylate, propyl methacrylate, n-butyl methacrylate, isobutyl methacrylate and n-octyl methacrylate , dodecyl methacrylate, 2-ethylhexyl methacrylate, stearyl methacrylate, phenyl methacrylate, dimethylaminoethyl methacrylate and diethylaminoethyl methacrylate; acrylates such as methyl acrylate, ethyl acrylate, n-butyl acrylate, isobutyl acrylate, propyl acrylate, n-octyl acrylate, dodecyl acrylate, 2-ethylhexyl acrylate, stearyl acrylate, 2-chloroethyl acrylate and phenyl acrylate; vinyl ethers such as vinyl methyl ether, vinyl ethyl ether and vinyl isobutyl ether; vinyl ketones such as vinyl methyl ketone, vinyl hexyl ketone and methyl isopropenyl ketone; N-vinyl compounds such as N-vinylpyrrole, N-vinylcarbazole, N-vinylindole and N-vinylpyrrolidone; vinylnaphthalene; and derivatives of acrylic acid or methacrylic acid such as acrylonitrile, methacrylonitrile and acrylamide.

[0147] The following are additional examples: unsaturated dibasic acids, such as maleic acid, citraconic acid, itaconic acid, alkenyl succinic acid, fumaric acid, and mesaconic acid; unsaturated dibasic anhydrides, such as maleic anhydride, citraconic anhydride, itaconic anhydride, and alkenyl succinic anhydride; half esters of unsaturated dibasic acids, such as methyl half ester of maleic acid, ethyl half ester of maleic acid, butyl half ester of maleic acid, methyl half ester of citraconic acid, ethyl half ester of citraconic acid, butyl half ester of citraconic acid, methyl half ester of itaconic acid, methyl half ester of alkenyl succinic acid, The present invention relates to esters of unsaturated dibasic acids, such as dimethyl maleate and dimethyl fumarate; α,β-unsaturated acids, such as acrylic acid, methacrylic acid, crotonic acid and cinnamic acid; anhydrides of α,β-unsaturated acids, such as crotonic anhydride and cinnamic anhydride; anhydrides between α,β-unsaturated acids and lower fatty acids; and carboxyl-containing monomers, such as alkenylmalonic acid, alkenylglutaric acid and alkenyladipic acid, and their anhydrides and monoesters.

[0148] Further examples are esters of acrylic acid or methacrylic acid, such as 2-hydroxyethyl acrylate, 2-hydroxyethyl methacrylate and 2-hydroxypropyl methacrylate; and hydroxyl-containing monomers, such as 4-(1-hydroxy-1-methylbutyl)styrene and 4-(1-hydroxy-1-methylhexyl)styrene.

[0149] The vinyl polymer part preferably has a structure in which at least one selected from the group consisting of acrylates and methacrylates is polymerized. The vinyl polymer part preferably has a structure in which at least one selected from the group consisting of acrylates and methacrylates is polymerized, and a structure in which styrene is polymerized.

[0150] The total amount of the structure in which at least one selected from the group consisting of acrylic acid esters and methacrylic acid esters is polymerized in the vinyl polymer site is preferably 50% by mass to 98% by mass, and more preferably 70% by mass to 98% by mass.

[0151] The binder resin preferably has both a crosslinked structure between the vinyl polymer portion and the non-crystalline polyester portion and a crosslinked structure in the non-crystalline polyester portion. This makes it easier to control the storage elastic modulus G' and the toner wet spreading index within the above ranges.

[0152] Crystalline polyester resin

[0153] The toner particles preferably contain a crystalline polyester resin.

[0154] Here, the crystalline polyester is defined as a polyester resin having a clear endothermic peak when measured by differential scanning calorimetry (DSC).

[0155] The crystalline polyester resin will be described below.

[0156] Known crystalline polyester resins can be used. For example, polycondensation products of aliphatic dicarboxylic acids and aliphatic diols can be mentioned.

[0157] The crystalline polyester resin is preferably a polycondensation product of an aliphatic dicarboxylic acid and an aliphatic diol with at least one selected from the group consisting of an aliphatic monocarboxylic acid and an aliphatic monoalcohol. The crystalline polyester resin is more preferably a polycondensation product of an aliphatic dicarboxylic acid and an aliphatic diol with an aliphatic monocarboxylic acid.

[0158] Examples of the aliphatic dicarboxylic acid include aliphatic dicarboxylic acids having 2 to 20 carbon atoms. Examples thereof include oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, dodecanedioic acid, hexadecanedioic acid, octadecanedioic acid, and the like.

[0159] Examples of the aliphatic diol include aliphatic diols having 2 to 20 carbon atoms. Examples thereof include ethylene glycol, diethylene glycol, triethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, dipropylene glycol, trimethylene glycol, neopentyl glycol, 1,4-butylene glycol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, 1,16-hexadecanediol, 1,18-octadecanediol, and the like.

[0160] Examples of the aliphatic monocarboxylic acid include aliphatic monocarboxylic acids having 6 to 20 carbon atoms. Examples thereof include caproic acid, heptanoic acid, octanoic acid, nonanoic acid, decanoic acid (capric acid), dodecanoic acid (lauric acid), tetradecanoic acid (myristic acid), hexadecanoic acid (palmitic acid), octadecanoic acid (stearic acid), eicosanoic acid (arachidic acid), behenic acid (behenic acid), and tetracosanoic acid (lignoceric acid).

[0161] Examples of the aliphatic monohydric alcohol include aliphatic monohydric alcohols having 6 to 20 carbon atoms, and examples thereof include octanol, undecanol, lauryl alcohol, tridecanol, myristyl alcohol, pentadecanol, palmityl alcohol, heptadecanol, stearyl alcohol, nonadecanol, arachidyl alcohol, and the like.

[0162] The crystalline polyester resin is preferably a polycondensation product of an alcohol component containing an aliphatic diol and an acid component containing an aliphatic dicarboxylic acid. When the carbon number of the aliphatic diol is C1 and the carbon number of the aliphatic dicarboxylic acid is C2, the sum of C1 and C2 is preferably 10 to 16, and more preferably 12 to 16.

[0163] When a plurality of aliphatic diols and / or aliphatic dicarboxylic acids are used, the carbon numbers of each are average values ​​of mass fractions.

[0164] The sum of C1 and C2 being 10 to 16 means that the total number of carbon atoms of the aliphatic diol and the aliphatic dicarboxylic acid constituting the crystalline polyester resin is relatively small.

[0165] By reducing the sum of C1 and C2 to the above range, the number of ester groups contained in the crystalline polyester resin increases. The increase in the number of ester groups increases the polarity of the crystalline polyester resin. As a result, the plasticization speed of the binder resin becomes fast, and the effect of the present invention is easily exhibited.

[0166] The crystalline polyester resin is a polycondensation product of an alcohol component containing an aliphatic diol and an acid component containing an aliphatic dicarboxylic acid, and preferably has at least one of a structure in which an aliphatic monocarboxylic acid is condensed at a terminal and a structure in which an aliphatic monoalcohol is condensed at a terminal.

[0167] The carbon number C3 of at least one of the structure in which an aliphatic monocarboxylic acid is condensed and the structure in which an aliphatic monoalcohol is condensed is preferably 6 to 14.

[0168] The melting point of the crystalline polyester resin is preferably 65° C. to 100° C. The melting point is determined by the combination of the carboxylic acid component and the alcohol component used, and may be appropriately selected so as to fall within the above range.

[0169] The amount of the crystalline polyester resin is preferably 5 to 30 parts by mass, more preferably 8 to 30 parts by mass, even more preferably 10 to 25 parts by mass, and further preferably 10 to 20 parts by mass relative to 100 parts by mass of the binder resin.

[0170] The crystalline polyester resin can be produced by a conventional polyester synthesis method. For example, the crystalline polyester resin can be obtained by subjecting an acid component and an alcohol component to an esterification reaction or an ester exchange reaction, and then subjecting the acid component and an alcohol component to a polycondensation reaction under reduced pressure or by introducing nitrogen according to a conventional method.

[0171] In the esterification or transesterification reaction, a common esterification catalyst or transesterification catalyst such as sulfuric acid, tert-butyl butoxy titanium, dibutyl tin oxide, manganese acetate or magnesium acetate can be used as necessary. For polymerization, a conventional polymerization catalyst such as tert-butyl butoxy titanium, dibutyl tin oxide, tin acetate, zinc acetate, tin disulfide, antimony trioxide and germanium dioxide can be used. The polymerization temperature and the amount of the catalyst are not particularly limited and can be arbitrarily selected as required.

[0172] It is desirable that a titanium catalyst is used as the catalyst, and a chelate-type titanium catalyst is more desirable because the reactivity of the titanium catalyst is appropriate and a polyester having a molecular weight distribution desired in the present invention can be obtained.

[0173] Colorants

[0174] A colorant may be used in the toner. Examples of the colorant include the following organic pigments, organic dyes, and inorganic pigments.

[0175] Examples of cyan colorants include copper phthalocyanine compounds and derivatives thereof, anthraquinone compounds, and basic dye lake compounds.

[0176] Examples of the magenta colorant are listed below: condensed azo compounds, diketopyrrolopyrrole compounds, anthraquinone compounds, quinacridone compounds, basic dye lake compounds, naphthol compounds, benzimidazolone compounds, thioindigo compounds, and perylene compounds.

[0177] Examples of the yellow-based colorant include condensed azo compounds, isoindolinone compounds, anthraquinone compounds, azo metal complexes, methine compounds, and allylamide compounds.

[0178] Examples of the black colorant include carbon black, and those toned to black using the above-mentioned yellow colorant, magenta colorant, cyan colorant, and magnetic powder.

[0179] These colorants may be used alone or in mixture, and may also be used in a solid solution state.The colorant used in the present invention is selected from the viewpoints of hue angle, saturation, brightness, light resistance, OHP transparency, and dispersibility in toner particles.

[0180] The amount of the colorant is preferably 1 part by mass to 10 parts by mass relative to 100 parts by mass of the binder resin.

[0181] Magnetic particles

[0182] Magnetic particles can be used as black colorants.

[0183] When magnetic particles are used, it is preferred to have a core particle comprising a magnetic iron oxide particle and a coating layer provided on the surface of the core particle.

[0184] The core particles comprising magnetic iron oxide particles can be exemplified by magnetic iron oxides such as magnetite, hematite and ferrite and magnetic iron oxides containing other metal oxides, as well as by metals such as Fe, Co and Ni, and alloys of these metals with Al, Co, Cu, Pb, Mg, Ni, Sn, Zn, Sb, Be, Bi, Cd, Ca, Mn, Ti, W and V, and mixtures thereof.

[0185] The coating can evenly cover the entire surface of the core particle, or can cover the surface of the core particle in a partially exposed state. In any coating mode, the coating is preferably the outermost layer, and preferably thinly coats the surface of the core particle. Preferably, Si and Al are included as the elements forming the coating.

[0186] The formation method of the coating is not particularly limited, and a known method can be used. For example, after producing core particles containing magnetite, a silicon source or an aluminum source such as sodium silicate or aluminum sulfate is added to an aqueous solution of ferrous sulfate. Then, a coating containing a specific oxide on the surface of the core particles can be formed by blowing air while adjusting the pH and temperature of the mixed solution.

[0187] In addition, the thickness of the coating can be controlled by adjusting the addition amount of ferrous sulfate aqueous solution, sodium silicate and aluminum sulfate.

[0188] Furthermore, from the viewpoint of facilitating the formation of the above-mentioned coating layer and improving magnetic properties and coloring power, the magnetic particles preferably have an octahedral shape.

[0189] As a method for controlling the shape of the magnetic particles, a conventionally known method can be adopted. For example, by adjusting the pH during the wet oxidation reaction to 9 or more in the production of the core particles, the magnetic particles can be formed into an octahedral shape.

[0190] From the viewpoint of low-temperature fixability, the amount of the magnetic particles is preferably 25 parts by mass to 100 parts by mass, and more preferably 30 parts by mass to 90 parts by mass relative to 100 parts by mass of the binder resin.

[0191] Other constituent materials of toner

[0192] It is preferred that the toner particles contain a releasing agent (wax) to give the toner releasability.

[0193] The following are specific examples of waxes.

[0194] Oxidants of aliphatic hydrocarbon waxes, such as oxidized polyethylene waxes and their block copolymers; waxes whose main components are fatty acid esters, such as carnauba wax, sasol wax and montanate wax; and waxes provided by partial or complete deacidification of fatty acid esters, such as deacidified carnauba wax; saturated straight-chain fatty acids, such as palmitic acid, stearic acid and montanic acid; unsaturated fatty acids, such as brazilenic acid, eleostearic acid and octadecatetraenoic acid; saturated alcohols, such as stearyl alcohol, aralkyl alcohol, behenyl alcohol, carnauba alcohol, wax alcohol and myristyl alcohol; long-chain alkyl alcohols; polyols, such as sorbitol; fatty acid amides, such as linoleamide, oleamide and lauramide; saturated fatty acid bisamides, such as methylene bisstearamide, Ethylenebiscapric acid amide, ethylenebislauric acid amide and hexamethylenebisstearic acid amide; unsaturated fatty acid amides such as ethylenebisoleic acid amide, hexamethylenebisoleic acid amide, N,N'-dioleyl adipamide and N,N-dioleyl sebacic acid amide; aromatic bisamides such as meta-xylene distearamide and N,N-distearylisophthalamide; fatty acid metal salts (usually, called metal soaps) such as calcium stearate, calcium laurate, zinc stearate and magnesium stearate; waxes obtained by grafting aliphatic hydrocarbon waxes with vinyl monomers such as styrene or acrylic acid; partial esters between polyols and fatty acids, such as monoglyceride of behenic acid; and hydroxyl-containing methyl ester compounds obtained by hydrogenation of vegetable oils.

[0195] The following are specific examples: VISKOL (registered trademark) 330-P, 550-P, 660-P and TS-200 (Sanyo Chemical Industries, Ltd.); Hi-WAX 400P, 200P, 100P, 410P, 420P, 320P, 220P, 210P and 110P (Mitsui Chemicals, Inc.); Sasol H1, H2, C80, C105 and C77 (Sasol Wax GmbH); HNP-1, HNP-3, HNP-9, HNP-10, HNP-11 and HNP-12 (Nippon Seiro Co., Ltd.); UNILIN (registered trademark) 350, 425, 550 and 700, and UNICID (registered trademark) 350, 425, 550 and 700 (Toyo Petrolite Co., Ltd.); and Japan wax, beeswax, rice wax, candelilla wax and carnauba wax (Cerarica NODA Co., Ltd.).

[0196] From the viewpoint of low temperature fixing property, it is preferred that the melting point of the wax is 65.0° C. to 120.0° C. Furthermore, the difference between the melting point of the wax and the melting point of the crystalline polyester resin is preferably 0° C. to 25° C., and more preferably 0° C. to 35° C.

[0197] Compared with the crystalline polyester resin, the wax is more likely to crystallize in the toner particles at room temperature. By reducing the difference between the melting points, the crystallization of the crystalline polyester resin is promoted along with the crystallization of the wax, so that the following Tg1 can be easily controlled within a specific range.

[0198] The toner may include a charge control agent to stabilize its triboelectric charging behavior.

[0199] The content of the charge control agent, although also varying depending on its type and the properties of other constituent materials of the toner, is generally preferably 0.1 to 10 parts by mass, and more preferably 0.1 to 5 parts by mass, relative to 100 parts by mass of the binder resin.

[0200] As the charge control agent, charge control agents that control toner to negative chargeability and charge control agents that control toner to positive chargeability are known, and one alone or two or more of the various charge control agents may be used depending on the toner type and purpose.

[0201] The following are examples of charge control agents used to control toner to have negative charging properties:

[0202] Organometallic complexes (monoazo metal complexes, acetylacetonate metal complexes); metal complexes and metal salts of aromatic hydroxycarboxylic acids and aromatic dicarboxylic acids; aromatic monocarboxylic acids and polycarboxylic acids and their metal salts and anhydrides; and phenol derivatives such as esters and bisphenols.

[0203] The following are examples of the charge control agent used to control the toner to have positive charging performance:

[0204] Aniline black and its modified products by fatty acid metal salts; quaternary ammonium salts such as tributylbenzylammonium 1-hydroxy-4-naphthalenesulfonate and tetrabutylammonium tetrafluoroborate, and their analogs; onium salts such as phosphonium salts, and their lake pigments; triphenylmethane dyes and their lake pigments (the lake agents can be exemplified by phosphotungstic acid, phosphomolybdic acid, phosphotungstomolybdic acid, tannic acid, lauric acid, gallic acid, ferrocyanic acid and ferrocyanide compounds); and metal salts of higher fatty acids.

[0205] Among the above, for example, nigrosine series compounds and quaternary ammonium salts are preferred.

[0206] A charge control resin may also be used, and it may also be used in combination with the above-mentioned charge control agent. Specific examples of the charge control agent are as follows:

[0207] Spilon Black TRH, T-77, T-95 and TN-105 (Hodogaya Chemical Co., Ltd.); BONTRON (registered trademark) S-34, S-44, E-84 and E-88 (Orient Chemical Industries Co., Ltd.); TP-302 and TP-415 (Hodogaya Chemical Co., Ltd.); BONTRON (registered trademark) N-01, N-04, N-07 and P-51 (Orient Chemical Industries Co., Ltd.); and Copy Blue PR (Clariant International Ltd,).

[0208] The toner may have silica fine particles or the like as an external additive to improve charging stability, durable developing properties, fluidity, and durability.

[0209] The specific surface area of ​​the silica fine particles by the BET method based on nitrogen adsorption is preferably 30 m 2 / g or more and more preferably 50m 2 / g to 400m 2The content of the silica fine particles is preferably 0.01 parts by mass to 8.00 parts by mass and more preferably 0.10 parts by mass to 5.00 parts by mass relative to 100 parts by mass of the toner particles.

[0210] The BET specific surface area of ​​the silica fine particles can be measured by a multipoint BET method through adsorption of nitrogen on the surface of the silica fine particles using, for example, Autosorb 1 specific surface area analyzer (Yuasa Ionics Co., Ltd.), GEMINI 2360 / 2375 (Micromeritics Instrument Corporation), or TriStar-3000 (Micromeritics Instrument Corporation).

[0211] For the purpose of controlling the triboelectric charging properties, it is optionally also preferred to treat the silica fine particles with a treating agent such as unmodified silicone varnish, various modified silicone varnishes, unmodified silicone oil, various modified silicone oils, silane coupling agents, functional group-containing silane compounds or other silicone compounds, or with a combination of different treating agents.

[0212] Other external additives may also be added to the toner on an optional basis. These external additives may be exemplified by resin fine particles and inorganic fine particles as auxiliary charging agents, agents imparting conductivity, agents imparting fluidity, anti-caking agents, release agents for hot roller fixing, lubricants, abrasives, and the like.

[0213] The lubricant can be exemplified by polyvinyl fluoride powder, zinc stearate powder, and polyvinylidene fluoride powder. The abrasive can be exemplified by cerium oxide powder, silicon carbide powder, and strontium titanate powder. Among the above, strontium titanate powder is preferred.

[0214] The toner can be used as a two-component developer by mixing with a carrier. For example, a common carrier such as ferrite and magnetite, or a resin-coated carrier can be used as the above-mentioned carrier. A binder-type carrier in which a magnet is dispersed in a resin can also be used.

[0215] The resin-coated carrier includes carrier core particles, and a coating, that is, a resin coated on the surface of the carrier core particles. The resin used for the coating can be exemplified by styrene-acrylic resins such as styrene-acrylate copolymers and styrene-methacrylate copolymers; acrylic resins such as acrylate copolymers and methacrylate copolymers; fluororesins such as polytetrafluoroethylene, chlorotrifluoroethylene polymers and polyvinylidene fluoride; silicone resins; polyester resins; polyamide resins; polyvinyl butyral; and aminoacrylate resins.

[0216] Other examples include ionomer resins and polyphenylene sulfide resins. These resins may be used alone or in combination of two or more.

[0217] In the differential scanning calorimeter (DSC) measurement of the toner,

[0218] (i) the number of cold crystallization peaks in the range of 40°C to 120°C during cooling is X, and

[0219] (ii) When the number of endothermic peaks in the range of 40°C to 120°C during the second temperature increase is Y,

[0220] X and Y satisfy the following formulae (7) and (8). More preferably, the following formulae (7') and (8') are satisfied, and even more preferably X=1 and Y=2.

[0221] (7)X≥1

[0222] (8)Y≥X+1

[0223] (7')2≥X≥1

[0224] (8')Y=X+1.

[0225] By utilizing the above characteristics, the crystallization rate of the crystalline polyester resin is increased and the heat-resistant storage stability is improved. The reason for this is considered to be as follows.

[0226] As described above, the crystalline polyester resin takes a long time to crystallize. Generally, the crystalline polyester resin that is not completely crystallized lowers the glass transition temperature (Tg) of the toner, thereby tending to deteriorate the heat-resistant storage stability.

[0227] Preferably, the toner particles include a crystalline polyester resin and an easily oriented wax. It is believed that such a wax can promote the crystallization rate of the crystalline polyester resin. It is also believed that when X and Y satisfy the above relationship, the crystalline polyester resin and the wax are oriented.

[0228] The toner particles preferably contain a crystalline polyester resin.

[0229] Furthermore, in differential scanning calorimetry of toner,

[0230] The temperature was increased from 25° C. to 120° C. at a rate of 1000° C. / sec (first temperature increasing process).

[0231] The temperature is maintained at 120°C for 100 milliseconds (0.100 seconds) (high temperature holding process), and then cooled to 25°C at a rate of 1000°C / sec (cooling process), and then

[0232] The temperature is raised to 120°C at a rate of 1000°C / sec (second temperature raising process), and

[0233] When the glass transition temperature during the first heating is Tg1 (°C), and the glass transition temperature during the second heating is Tg2 (°C),

[0234] It is preferable to satisfy the following formulas (9) and (10).

[0235] (9) 65℃≤Tg1≤85℃

[0236] (10)7℃≤Tg1-Tg2≤30℃.

[0237] Such DSC measurement conditions are equivalent to the heat received by the toner from the fixing device. Specifically, the temperature and time of the high temperature holding process are adjusted so that heat can be received at 120° C. for 100 milliseconds. The glass transition temperature Tg2 obtained by measurement in the second temperature rising process shows the degree of plasticity of the crystalline polyester resin to the toner when receiving heat.

[0238] That is, the increase in Tg1-Tg2 indicates that the crystalline polyester resin can sufficiently plasticize the toner even when heated for a very short time.

[0239] Here, in order to reduce the heat outside the high temperature holding process, the temperature rise rate is set to a very high value of 1000°C / sec so that the toner does not receive excessive heat outside the high temperature holding process. In addition, in order to make the plasticity of the crystalline polyester resin to the toner close to the plasticity when passing through the fixing device, the cooling rate is set to a very high value of 1000°C / sec.

[0240] This is because the crystalline polyester plasticizes the toner when held at 120° C. for 100 milliseconds, but in the case where the cooling rate is low, the crystalline polyester crystallizes during the cooling process. Therefore, Tg2 obtained in the second temperature increase process is affected by two factors, namely, the plasticization effect of the high temperature holding process and the crystallization of the cooling process, and there is a high probability that the desired state cannot be measured.

[0241] Shown below are measurement conditions that are typically used for routine measurements compared to such DSC measurement conditions:

[0242] The temperature was increased from 25°C to 120°C at a rate of 10°C / min (the first heating process);

[0243] Keep the temperature at 120°C for 5 minutes (high temperature holding process);

[0244] Cool down to 25°C at a rate of 10°C / min (cooling process), then

[0245] The temperature was increased to 120° C. at a rate of 10° C. / min (the second temperature increasing process).

[0246] In this measurement, since the high temperature holding process is longer than that in the conditions of the present invention, it is likely that the crystalline polyester resin will sufficiently plasticize the toner even if the toner is constructed so that the plasticization speed of the toner is insufficient.

[0247] Meanwhile, in the present invention, it is shown that the crystalline polyester can plasticize the toner even in a very short high-temperature holding process.

[0248] Formula (9) indicates that the glass transition temperature Tg1 (° C.) of the toner in the first temperature increase process is 65° C. to 85° C. Tg1 is higher than the result obtained from Tg measured at a temperature increase rate of 10° C. / min as a conventional measurement condition.

[0249] In the case where Tg1 is 65°C or more, a toner having satisfactory storability can be obtained. In addition, in the case where Tg1 is 85°C or less, a toner having satisfactory low-temperature fixability can be obtained. Tg1 is preferably 70°C to 80°C.

[0250] Formula (10) indicates that the difference between the glass transition temperature Tg2 of the toner in the second temperature rising process and the glass transition temperature Tg1 of the toner in the first temperature rising process is 7° C. to 30° C. When formula (10) is satisfied, it means that the crystalline polyester resin can plasticize the toner even at a very short high temperature holding time.

[0251] As a result, the toner can be fully plasticized in a very short time when the medium passes through the fixing device. For this reason, a toner that can simultaneously achieve both satisfactory low-temperature fixability and suppression of solid image density unevenness can be obtained. Tg1-Tg2 is preferably 10° C. to 30° C. Tg1-Tg2 can be controlled by, for example, changing the composition of the resin component in the toner or the composition of the fixing aid.

[0252] Tg2 is preferably 40°C to 75°C, and more preferably 45°C to 70°C.

[0253] A preferred composition of the toner is described below.

[0254] In order to satisfy the formulas (9) and (10), it is preferred that the crystalline polyester resin plasticizes the toner even at a very short high temperature holding time. This can be achieved by making the crystalline polyester resin easily compatible with the binder resin of the toner when receiving heat.

[0255] Examples of specific means include selecting a compound constituting the crystalline polyester resin, selecting a compound constituting the binder resin, and making the solubility parameter SP values ​​of the crystalline polyester resin and the binder resin close to each other; improving the dispersibility of the crystalline polyester resin in the toner particles; and improving the crystallinity of the crystalline polyester. By combining these, formulas (9) and (10) can be satisfied.

[0256] In the temperature T (°C)-storage elastic modulus G' (Pa) curve obtained by measuring the toner at a temperature increase rate of 2.0°C / min using a flat plate rotational rheometer, the storage elastic modulus is 1.0×10 3 The temperature at Pa is T1 (℃).

[0257] When there is an endothermic peak in the range of 30°C to 120°C on a DSC curve of the toner obtained by differential scanning calorimetry and the peak temperature of the peak existing on the lowest temperature side of the endothermic peak is T2 (°C), the following formula (11) is satisfied.

[0258] (11)T1-T2≥40.

[0259] Generally, a binder resin (e.g., a non-crystalline resin) has a glass transition point (Tg). The viscosity of the binder resin exceeding Tg gradually decreases, but the rate of viscosity decrease is slow. Meanwhile, a crystalline material (crystalline polyester resin and wax, etc.) has a melting point inherent to the material, and when the crystalline material reaches a temperature above the melting point, the viscosity drops sharply.

[0260] This behavior is the same when the toner includes a crystalline material, and if the difference in viscosity between the crystalline material and the binder resin is too large, the crystalline material separates from the binder resin, which can cause uneven solid image density. That is, it is preferred that the difference between the melting point of the crystalline material and the temperature at which the toner reaches a specific viscosity is small. When T1-T2 satisfies the relationship of formula (11), uneven solid image density can be suppressed.

[0261] More preferably, T1-T2 is 0-35.

[0262] Method for producing toner

[0263] The production method of the toner is not particularly limited, and a known production method can be adopted. Hereinafter, a method of producing the toner through a melt-kneading step and a pulverizing step will be specifically shown, but is not limited to this method.

[0264] For example, the binder resin, and optionally the crystalline polyester resin, the colorant, the release agent, the charge control agent and other additives can be fully mixed using a mixer such as a Henschel mixer or a ball mill (mixing step). The resulting mixture can be melt-kneaded using a heated kneading machine such as a twin-screw kneading extruder, a hot roll, a kneader or an extruder (melt-kneading step).

[0265] The obtained melt-kneaded material can be cooled and solidified, then pulverized using a pulverizer (pulverization step), followed by classification using a classifier (classification step) to obtain toner particles. The toner particles can also be optionally mixed with an external additive using a mixer such as a Henschel mixer to obtain a toner.

[0266] Examples of the mixer include: FM mixer (Nippon Coke & Engineering Co., Ltd.); Supermixer (Kawata Mfg. Co., Ltd.); Ribocone (Okawara Corporation); Nauta mixer, Turbulizer and Cyclomix (Hosokawa Micron Corporation); Spiral Pin Mixer (Pacific Machinery & Engineering Co., Ltd.); and Loedige Mixer (Matsubo Corporation).

[0267] Examples of kneading equipment include KRC kneader (Kurimoto, Ltd.); Buss Ko-Kneader (Buss Corp.); TEM extruder (Toshiba Machine Co., Ltd.); TEX twin-screw kneader (The Japan SteelWorks, Ltd.); PCM kneader (Ikegai Ironworks Corporation); three-roll mill, mixing roll mill, and kneader (Inoue Manufacturing Co., Ltd.); Kneadex (Mitsui Mining Co., Ltd.); MS type pressure kneader and Kneader-Ruder (Moriyama Mfg. Co., Ltd.); and Banbury mixer (Kobe Steel, Ltd.).

[0268] Examples of pulverizers include Counter Jet Mill, Micron Jet, and Inomizer (Hosokawa Micron Corporation); IDS mill and PJM Jet Mill (Nippon Pneumatic Mfg. Co., Ltd.); Cross Jet Mill (Kurimoto, Ltd.); Ulmax (Nisso Engineering Co., Ltd.); SK Jet-O-Mill (Seishin Enterprise Co., Ltd.); Kryptron (Kawasaki Heavy Industries, Ltd.); Turbo Mill (Turbo Kogyo Co., Ltd.), and Super Rotor (Nisshin Engineering Inc.).

[0269] Examples of classifiers include Classiel, Micron Classifier, and Spedic Classifier (Seishin Enterprise Co., Ltd.); Turbo Classifier (Nisshin Engineering Inc.); Micron Separator, Turboplex (ATP), and TSP Separator (Hosokawa Micron Corporation); Elbow Jet (Nittetsu Mining Co., Ltd.); Dispersion Separator (Nippon Pneumatic Mfg. Co., Ltd.); and YM Microcut (Yasukawa Shoji Co., Ltd.).

[0270] The following screening devices can be used to screen out coarse particles: Ultrasonic (Koei Sangyo Co., Ltd.), Rezona Sieve and Gyro-Sifter (Tokuju Corporation), Vibrasonic System (Dalton Co., Ltd.), Sonilean (Sintokogio, Ltd.), Turbo Screener (Turbo Kogyo Co., Ltd.), Microsifter (Makino Mfg. Co., Ltd.), and circular vibrating screen.

[0271] An annealing step may be performed in order to facilitate control of the minimum value of the amount of change (dG' / dT) of the storage elastic modulus G' with respect to the temperature T. The annealing step is a step of crystallizing a crystalline material such as a crystalline polyester resin in toner particles.

[0272] In particular, when a crystalline polyester resin that easily plasticizes the binder resin is used, in order to sufficiently promote crystallization of the crystalline polyester resin at normal temperature, the crystalline polyester resin is preferably crystallized through an annealing step.

[0273] The measurement methods of physical properties are described below.

[0274] Storage elastic modulus G'(80℃) and storage elastic modulus G'(120℃) measurement method

[0275] (1) Preparation of measurement samples

[0276] A cylindrical sample having a diameter of 8 mm and a height of 2.0±0.3 mm is prepared as a measurement sample by compression molding about 0.15 g (variable depending on the specific gravity of the sample) of toner or THF-insoluble matter of toner at 20 MPa for 60 seconds using a tablet molding press in an environment of 25°C.

[0277] (2) Install the sample

[0278] A flat plate type rotational rheometer "ARES" (manufactured by TA INSTRUMENTS) was used as a measuring device. The sample was mounted on a parallel plate, and the axial force (Axial Force) was adjusted to 250-300 and held (Hold). Next, the temperature was raised from room temperature (25°C) to 65°C (appropriately adjusted within the range of toner Tg+5°C to Tg+10°C) and held at this temperature for 10 minutes. Then, the sample shape was adjusted, and the sample was cooled to 30°C.

[0279] (3) Measurement

[0280] The measurement was performed under the following conditions.

[0281] Use parallel plates with a diameter of 8 mm.

[0282] The frequency is set to 6.28 rad / sec (1.0 Hz).

[0283] The initial value of applied strain (Strain) was set to 0.1%.

[0284] ·Measured at a ramp rate of 2.0°C / min between 50°C and 120°C and a ramp rate of 2.0°C / min between 120°C and 50°C. In addition, measured under the following auto-strain mode setting conditions. Measured in auto-strain mode.

[0285] The maximum strain (Max Applied Strain) was set to 20.0%.

[0286] The maximum torque (Max Allowed Torque) is set to 200.0 g·cm, and the minimum torque (Min Allowed Torque) is set to 0.2 g·cm.

[0287] The strain adjustment is set to 20.0% of the current strain. During the measurement, the automatic tension adjustment mode is used.

[0288] ·Auto Tension Direction is set to Compression.

[0289] • Initial Static Force was set to 10.0 g, and AutoTension Sensitivity was set to 40.0 g.

[0290] The operating conditions of Auto Tension are set to 1.0×10 2 (Pa) or above.

[0291] The storage elastic modulus G'(80°C) and the storage elastic modulus G'(120°C) were obtained from the temperature T(°C)-storage elastic modulus G'(Pa) curve obtained by the above method.

[0292] Furthermore, dG' / dT was calculated for every two consecutive plots, and the minimum value of the amount of change (dG' / dT) of the storage elastic modulus G' with respect to the temperature T in the range of 60°C to 80°C was obtained.

[0293] In addition, the storage elastic modulus is read from the obtained temperature T (°C)-storage elastic modulus G' (Pa) curve to become 1.0×10 3 Temperature T1 (°C) at Pa.

[0294] S2 / S1×1 / R1 measurement method

[0295] The projected area S1 of the toner at 80° C., the radius R1 of the toner at 80° C., and the projected area S2 of the toner at 120° C. are measured in the following manner.

[0296] (1) Preparation of measurement samples

[0297] Premium Presentation 120g Laser Paper (HP) was cut into 10 mm squares, and toner was attached to the Premium Presentation 120g Laser Paper (HP). A cotton swab was used to attach the toner, and the toner was attached in such a manner that each particle was scattered on the Premium Presentation 120g Laser Paper (HP).

[0298] (2) Measurement

[0299] A high-quality presentation 120g laser paper (HP) with toner attached was placed on a heating plate (Linkam microscope cooling and heating stage TH-600PM). The temperature of the heating plate was then raised at 10°C / min, and still images at 80°C and 120°C were captured while observing with an optical microscope. Next, the projection area S1 of the toner at 80°C, the radius R1 of the projection area of ​​the toner at 80°C, and the projection area S2 of the toner at 120°C were calculated from the captured still images using image analysis software (Image J).

[0300] S1, R1, and S2 are calculated as the arithmetic mean values ​​of 100 particles. When the toner has a non-spherical shape, the toner radius is calculated using the average value of the major axis and the minor axis of the toner particles as the toner diameter.

[0301] Measurement of glass transition temperatures Tg1 and Tg2

[0302] The glass transition temperature Tg1 (° C.) and the glass transition temperature Tg2 (° C.) were measured using a differential scanning calorimeter “FlashDSC1 STARe System” (manufactured by METTLER TOLEDO).

[0303] Measurement procedures

[0304] The toner is placed on a dedicated chip sensor that has been temperature-calibrated in advance. The temperature control of the chip sensor is performed in the following manner.

[0305] The temperature was maintained at 25°C for 10 seconds, and then increased to 120°C at a temperature increase rate of 1000°C / sec (first temperature increase process). After the temperature was maintained at 120°C for 100 milliseconds (high temperature maintenance process), cooling was performed to 25°C at a cooling rate of 1000°C / sec (cooling process). After the temperature was maintained at 25°C for 100 milliseconds, the temperature was increased to 120°C at a temperature increase rate of 1000°C / sec (second temperature increase process).

[0306] In the above temperature control, the glass transition temperature Tg1 (° C.) is calculated from the temperature increase curve showing the amount of endothermic heat obtained in the first temperature increase process.

[0307] In addition, the glass transition temperature Tg2 (° C.) was calculated from the temperature increase curve showing the amount of endothermic heat obtained in the second temperature increase process.

[0308] Method for measuring the content of ethyl acetate insoluble matter

[0309] About 1.5 g of the toner (W1 [g]) is accurately weighed and introduced into a pre-weighed extraction thimble (product name: No. 86R, size 28×100 mm, Toyo Roshi Kaisha, Ltd.), and placed in a Soxhlet extractor.

[0310] The extraction was performed for 18 hours using 200 mL of ethyl acetate as the solvent. Here, the extraction was performed at a reflux rate that provided a solvent extraction cycle of about once every 5 minutes.

[0311] After the extraction was completed, the extraction thimble was removed and air-dried, followed by vacuum drying at 50° C. for 24 hours. The mass of the extraction thimble containing the extraction residue was measured, and the mass of the extraction residue was calculated by subtracting the mass of the extraction thimble (W2 [g]).

[0312] Then, the content (W3 [g]) of components other than the binder resin is found using the following procedure.

[0313] About 2 g of toner (Wa [g]) was accurately weighed into a pre-weighed 30 mL magnetic crucible.

[0314] A magnetic crucible is placed in an electric furnace and heated at about 900°C for about 3 hours; cooled in the electric furnace; cooled in a dryer at room temperature for more than 1 hour; the mass of the crucible containing the pyrolysis residue is measured; and the pyrolysis residue (Wb[g]) is obtained by subtracting the mass of the crucible.

[0315] The mass (W3 [g]) of the pyrolysis residue in the sample W1 [g] was calculated using the following formula (A).

[0316] W3=W1×(Wb / Wa)(A)

[0317] In this case, the content of the ethyl acetate-insoluble matter in the binder resin is calculated using the following formula (B).

[0318] Ethyl acetate insoluble matter in binder resin = {(W2-W3) / (W1-W3)}×100(B)

[0319] Method for measuring the amount of tetrahydrofuran (THF) insoluble matter

[0320] The amount of THF-insoluble matter derived from the resin was found by the same method as in <Method of measuring ethyl acetate-insoluble matter>, except that the solvent was changed to THF.

[0321] In the process of obtaining the THF-insoluble matter, the storage elastic modulus G′ (120° C.) can be measured by using the above-mentioned method of the plate type rotational rheometer on a sample dried at 50° C. in vacuum for 24 hours after Soxhlet extraction.

[0322] Measurement of peak temperature T2

[0323] In a DSC curve of the toner obtained by differential scanning calorimetry, a peak temperature T2 (° C.) of a peak existing on the lowest temperature side among endothermic peaks in the range of 30° C. to 120° C. is measured in the following manner.

[0324] The measurement was performed using a differential scanning calorimeter "Q1000" (manufactured by TA Instruments) in accordance with ASTM D3418-82. The melting points of indium and zinc were used for temperature correction of the detection unit of the apparatus, and the heat of fusion of indium was used for correction of heat amount.

[0325] Specifically, about 5 mg of the measurement sample was accurately weighed and put into an aluminum pan, an empty aluminum pan was used as a control, and the measurement was performed at a temperature increase rate of 10° C. / min in the measurement temperature range of 30° C. to 120° C. at normal temperature and humidity. The temperature of the peak top existing on the lowest temperature side among the endothermic peaks in the measurement temperature range of 30° C. to 120° C. in the DSC curve obtained during the temperature increase was taken as T2 (° C.).

[0326] Measurement of the number of cold crystallization peaks X and the number of endothermic peaks Y during the second heating period in DSC measurement

[0327] The number X of cold crystallization peaks and the number Y of endothermic peaks during the secondary temperature increase are measured in the following manner.

[0328] The measurement was performed using a differential scanning calorimeter "Q1000" (manufactured by TA Instruments) in accordance with ASTM D3418-82. The melting points of indium and zinc were used for temperature correction of the detection unit of the apparatus, and the heat of fusion of indium was used for correction of heat amount.

[0329] Specifically, about 5 mg of the measurement sample was accurately weighed and placed in an aluminum pan, an empty aluminum pan was used as a control, and the measurement was performed at a temperature increase rate of 10°C / min in the measurement temperature range of 30°C to 180°C under normal temperature and humidity. During the measurement, the temperature was once increased to 180°C, then decreased to 30°C at a rate of 10°C / min, and then increased again.

[0330] In the DSC curve obtained in the cooling process, the number of exothermic peaks in the temperature range of 40°C to 120°C is taken as the number of cold crystallization peaks X. In addition, in the DSC curve obtained in the second temperature increase process, the number of endothermic peaks in the temperature range of 40°C to 120°C is taken as the number of endothermic peaks Y during the second temperature increase.

[0331] Measuring C1 and C2 from toner

[0332] The molecular structure of the crystalline polyester resin can be confirmed by NMR measurement using a solution or solid sample, and can also be confirmed by known analytical methods such as X-ray diffraction, GC / MS, LC / MS and IR measurement. In addition, a known method can be used to separate the crystalline polyester resin from the toner.

[0333] Specifically, the separation operation is performed in the following manner. First, the toner is dispersed in ethanol as a poor solvent for the toner, and the temperature is raised to a temperature exceeding the melting point of the crystalline polyester resin. At this time, pressure may be applied as needed. At this time point, the crystalline polyester resin having a temperature exceeding the melting point is melted. Thereafter, the crystalline polyester resin may be collected from the toner by solid-liquid separation.

[0334] wherein an acrylate and a methacrylate selected from the vinyl polymer moiety of the hybrid resin contained in the toner are used. Measurement of the amount of at least one polymerized structure of the group consisting of acrylic esters

[0335] The confirmation can be made by NMR measurement using a solid sample, and can also be made by known analytical methods such as X-ray diffraction, GC / MS, LC / MS, and IR measurement.

[0336] Measurement of the amount of non-crystalline polyester site of hybrid resin contained in toner

[0337] The confirmation can be carried out by NMR measurement using a solid sample, and can also be carried out by known analytical methods such as X-ray diffraction, GC / MS, LC / MS and IR measurement.

[0338] Example

[0339] The present invention will be specifically described below based on the following examples. However, the present invention is not limited thereto. In the following formulations, parts and % are based on mass unless otherwise specified.

[0340] Production Example of Long-Chain Alkyl Monomer (W-1)

[0341] A total of 1200 parts of chain saturated hydrocarbons having an average carbon number of 35 were placed in a glass cylindrical reaction container, and 38.5 parts of boric acid were added at a temperature of 140° C. Immediately thereafter, a mixed gas of 50% by volume of air and 50% by volume of nitrogen in which the oxygen concentration was about 10% by volume was blown in at a rate of 20 L / min, and the reaction was performed at 200° C. for 3.0 hours. After the reaction, warm water was added to the reaction solution, hydrolysis was performed at 95° C. for 2 hours, the product was allowed to stand, and then the reaction product (modified product) of the upper layer was obtained.

[0342] A total of 20 parts of the modified products obtained were added to 100 parts of n-hexane and purified to dissolve and remove a portion of the unmodified components to obtain a long-chain alkyl monomer (W-1). The long-chain alkyl monomer (W-1) had a modification rate of 93.6% by mass, that is, it contained 6.4% by mass of aliphatic hydrocarbons. Table 1 shows the physical properties.

[0343] [Table 1]

[0344]

[0345] In Table 1, W-2 (*) is UNILIN 700 (manufactured by Toyo Petrolite Co., Ltd.).

[0346] Production Example of Resin Composition (A-1)

[0347] · 20.0 mol parts of ethylene oxide adduct of bisphenol A (2.0 mol addition)

[0348] · Propylene oxide adduct of bisphenol A (2.3 mol addition) 80.0 mol parts

[0349] ·67.0 mol parts of terephthalic acid

[0350] · 7.0 mol of dodecanedioic acid

[0351] In addition to 96 parts of the above polyester monomer, a long-chain alkyl monomer (W-1) was added to obtain 5.0% by mass relative to the total polyester resin composition. The obtained mixture was charged into a four-necked flask, equipped with a decompression device, a water separator, a nitrogen introduction device, a temperature measuring device and a stirrer, and stirred at 160° C. under a nitrogen atmosphere.

[0352] Then, a mixture of 4 parts of vinyl polymerizable monomers (styrene: 10.0 mol parts, butyl acrylate: 90.0 mol parts) constituting a vinyl polymer site and 0.7 parts of benzoyl peroxide as a polymerization initiator was added dropwise from a funnel over 4 hours.

[0353] Then, after reacting at 160°C for 5 hours, the temperature was raised to 200°C, 0.15 parts of ditriethanolamine diisopropyl titanate and 0.01 parts of gallic acid were added, and then polycondensation was carried out at 230°C for 6 hours, and further reacted at 230°C and 8.0kPa for 1 hour. After cooling to 180°C, 0.01 parts of tert-butylcatechol and 15.0 mol parts of trimellitic anhydride were added relative to the polyester monomer, and the reaction time was adjusted to obtain the desired viscosity. After the reaction was completed, the resin composition (A-1) was taken out of the container, cooled and crushed to obtain the resin composition (A-1). Table 2 shows the physical properties.

[0354] Production Examples of Resin Compositions (A-2) to (A-12)

[0355] Resin compositions (A-2) to (A-12) were obtained in the same manner as in the production example of the resin composition (A-1) except that the monomer formulation shown in Table 3 was changed. Table 2 shows the physical properties.

[0356] Production Example of Resin Composition (A-13)

[0357] A total of 6550 g of the alcohol components shown in Table 3 and the carboxylic acid components other than trimellitic anhydride, 45 g of tin (II) 2-ethylhexanoate and 5 g of gallic acid were placed in a 10-liter four-necked flask equipped with a nitrogen inlet tube, a dehydration tube equipped with a fractionating tube through which hot water at 100° C. flowed, a stirrer and a thermocouple, and the flask was maintained at 180° C. for 1 hour under a nitrogen atmosphere, and then the temperature was increased from 180° C. to 230° C. at a rate of 10° C. / h, and then a polycondensation reaction was carried out at 230° C. for 6 hours.

[0358] After reacting at 230°C and 8.0 kPa for 1 hour, trimellitic anhydride was further reacted at 210°C, and the reaction time was adjusted to obtain the desired viscosity. After the reaction was completed, the resin composition was taken out of the container, cooled and pulverized to obtain a resin composition (A-13). Table 2 shows the physical properties.

[0359] Production Example of Resin Composition (A-14)

[0360] Among the monomers listed in Table 3, the raw material monomers of the polyester resin other than fumaric acid and trimellitic anhydride were put into a 10-liter four-necked flask equipped with a dehydration tube equipped with a nitrogen introduction tube, a stirrer and a thermocouple, and the temperature was raised to 160° C. in a jacketed resistance heater under a nitrogen atmosphere.

[0361] After that, a mixture of raw material monomers of the vinyl resin and a polymerization initiator was added dropwise through a dropping funnel over 1 hour. After the addition, the addition polymerization reaction was matured for 1 hour while maintaining the temperature at 160° C., then the temperature was raised to 200° C., and 0.15 parts of bistriethanolamine diisopropyl titanate and 0.015 parts of gallic acid were added to 100 parts of the monomers shown in Table 3. Then, a polycondensation reaction was performed at 235° C. for 6 hours, and further, the reaction was performed at 235° C. and 8.0 kPa for 1 hour.

[0362] After cooling to 180°C, 0.015 parts of tert-butylcatechol were added to 100 parts of fumaric acid and trimellitic anhydride shown in Table 3 and the monomers shown in Table 3, the temperature was raised from 180°C to 210°C at 10°C / h, and the reaction time was adjusted to obtain the desired viscosity. After the reaction was completed, the resin composition was taken out of the container, cooled and pulverized to obtain a resin composition (A-14). Table 2 shows the physical properties.

[0363] [Table 2]

[0364]

[0365] [Table 3]

[0366]

[0367] The abbreviations in Table 3 are as follows.

[0368] BPA-PO: Propylene oxide adduct of bisphenol A (2.3 mol addition)

[0369] BPA-EO: ethylene oxide adduct of bisphenol A (2.0 mole addition)

[0370] TPA: Terephthalic acid

[0371] IPA: Isophthalic acid

[0372] TMA: trimellitic anhydride

[0373] St:Styrene

[0374] BA: Butyl acrylate

[0375] In the tables, the numerical values ​​of monomers other than the long-chain alkyl monomers represent parts by mole.

[0376] *1: The mol parts of the monomers represent the ratio when the total amount of the monomers in the alcohol component (excluding the long-chain alkyl monomer) is 100 mol parts.

[0377] *2: The mol parts of the monomers indicate the ratio when the total amount of the monomers in the vinyl polymer site is 100 mol parts.

[0378] *3: PES / StAc ratio is the ratio of polyester part (excluding long-chain alkyl monomer) to vinyl polymer part (based on mass)

[0379] Production Example of Polyester Resin Composition (B-1)

[0380] The raw material monomers shown in Table 4 were introduced into a reactor equipped with a nitrogen introduction tube, a water separator, a stirrer and a thermocouple in the blending amounts (mol parts) shown in Table 4, and then 1.0 part of dibutyltin oxide was added as a catalyst relative to 100 parts of the total amount of the raw material monomers. At this time, W-2 (UNILIN 700 (Toyo Petrolite Co., Ltd.) was used as a long-chain alkyl monomer.

[0381] While stirring in a nitrogen atmosphere, the temperature in the reactor was raised to 150° C., and then polymerization was performed by distilling off water while heating from 150° C. to 200° C. at a temperature increase rate of 10° C. / hour.

[0382] After reaching 200° C., the pressure in the reactor was reduced to 5 kPa or less, and polycondensation was performed under the conditions of 200° C. and 5 kPa or less for 3 hours.

[0383] After the reaction was completed, it was taken out from the container, cooled and pulverized to obtain a polyester resin composition (B-1). The properties are shown in Table 5.

[0384] Production Example of Polyester Resin Composition (B-2)

[0385] In addition to the alcohol components shown in Table 4 and the carboxylic acid components other than adipic acid and trimellitic anhydride, 0.02 parts of tin (II) 2-ethylhexanoate and 0.025 parts of gallic acid relative to 100 parts of the monomers in Table 4 were placed in a 10-liter four-necked flask equipped with a nitrogen introduction tube, a dehydration tube equipped with a fractionating tube through which hot water at 100° C. flowed, a stirrer and a thermocouple, the flask was maintained at 180° C. for 1 hour under a nitrogen atmosphere, and then the temperature was increased from 180° C. to 230° C. at 10° C. / h, and then a polycondensation reaction was carried out at 230° C. for 6 hours.

[0386] After reacting at 230°C and 8.0 kPa for 1 hour, trimellitic anhydride was further reacted at 210°C, and the reaction time was adjusted to obtain the desired viscosity. After the reaction was completed, the resin composition was taken out of the container, cooled and pulverized to obtain a resin composition (B-2). Table 5 shows the physical properties.

[0387] [Table 4]

[0388]

[0389] The abbreviations in Table 4 are as follows.

[0390] BPA-PO: Propylene oxide adduct of bisphenol A (2.0 mol addition)

[0391] BPA-EO: ethylene oxide adduct of bisphenol A (2.0 mole addition)

[0392] EG: Ethylene glycol

[0393] TPA: Terephthalic acid

[0394] IPA: Isophthalic acid

[0395] TMA: trimellitic anhydride

[0396] In the tables, the numerical values ​​of monomers other than the long-chain alkyl monomers represent parts by mole.

[0397] *1: Parts by mole of a monomer indicates a ratio when the total amount of the monomers of the alcohol component (excluding the long-chain alkyl monomer) is 100 parts by mole.

[0398] [Table 5]

[0399]

[0400] Production Example of Crystalline Polyester (C-1)

[0401] 100.0 mol of ethylene glycol

[0402] ·Tetradecanedioic acid 90.0 mol

[0403] · 20.0 mol of lauric acid

[0404] A total of 0.2% by mass of dibutyltin oxide based on the total amount of the above monomer and the monomer was placed in a 10L four-necked flask equipped with a nitrogen introduction tube, a dehydration tube, a stirrer and a thermocouple, and a reaction was performed at 180°C for 4 hours. Then, the temperature was increased to 210°C at 10°C / 1 hour, and the temperature was maintained at 210°C for 8 hours, and then a reaction was performed at 8.3 kPa for 1 hour to obtain a crystalline polyester (C-1). Table 6 shows the physical properties.

[0405] Production Examples of Crystalline Polyesters (C-2) to (C-11)

[0406] Resin compositions (C-2) to (C-11) were obtained in the same manner as in the production example of the crystalline polyester (C-1), except that the monomer formulation shown in Table 6 was changed. Table 6 shows physical properties.

[0407] [Table 6]

[0408]

[0409] Production Example of Magnetic Particles 1

[0410] (1) Production of core particles

[0411] Add a total of 92L of Fe 2+ The concentration of 1.60mol / L of ferrous sulfate aqueous solution and 88L of 3.50mol / L of sodium hydroxide aqueous solution were mixed and stirred. The pH of the solution was 6.5. While the solution was kept at a temperature of 89°C and a pH of 9 to 12, 20L / min of air was blown in, thereby causing an oxidation reaction and generating core particles. When the ferrous hydroxide was completely consumed, the blowing of air was stopped and the oxidation reaction was terminated. The core particles obtained by magnetite had an octahedral shape.

[0412] (2) Formation of coating

[0413] After mixing 2.50 L of a 0.7 mol / L sodium silicate aqueous solution and 2.00 L of a 0.90 mol / L ferrous sulfate aqueous solution, 1.00 L of water was added to prepare 5.00 L of an aqueous solution, which was added to the reacted slurry containing 13,500 g of core particles while maintaining the pH at 7 to 9. Then, air was blown in at 10 L / min until the Fe in the slurry was reduced to 1.5 g. 2+ No more residue.

[0414] Subsequently, 0.70 L of a 1.50 mol / L aluminum sulfate aqueous solution and 2.00 L of a 0.90 mol / L ferrous sulfate aqueous solution were mixed, and then 1.00 L of water was added to prepare 5.00 L of an aqueous solution, which was added to the slurry containing the core particles after the reaction while the pH was maintained at 7 to 9. Then, air was blown in at 10 L / min until the Fe in the slurry was reduced to 1.50 mol / L. 2+ No more remained. The temperature of the slurry was maintained at 89° C. After mixing and stirring for 30 minutes, the slurry was filtered, washed and dried, thereby obtaining magnetic particles 1.

[0415] Magnetic Particle 1 had an octahedral shape, and the number average particle diameter (D1) of primary particles of Magnetic Particle 1 was 110 nm. Table 7 shows the physical properties of Magnetic Particle 1 obtained.

[0416] [Table 7]

[0417]

[0418] Release agent 1 to 4

[0419] The release agents shown in Table 8 were used.

[0420] [Table 8]

[0421]

[0422] Example 1

[0423]

[0424] The above materials were premixed with a Henschel mixer and then melt-kneaded at a preset temperature of 120°C with a twin-screw kneading extruder (PCM-30 model, manufactured by Ikegai Tekko KK).

[0425] The obtained kneaded product was cooled, coarsely pulverized with a hammer mill, and then annealed at a temperature of 50° C. and a relative humidity of 95% for 1 day.

[0426] Next, the coarsely pulverized product was pulverized with a mechanical pulverizer (T-250, manufactured by Turbo Kogyo Co., Ltd.), and the obtained finely pulverized powder was classified using a multi-classifier utilizing the Coanda effect to obtain negatively chargeable toner particles having a weight average particle size (D4) of 7.0 μm.

[0427] A total of 1.0 part of hydrophobic silica fine particles 1 [BET specific surface area 150 m 2 / g, 30 parts of hexamethyldisilazane (HMDS) and 10 parts of dimethyl silicone oil hydrophobized per 100 parts of silica fine particles] were externally added to 100 parts of toner particles and mixed with a Henschel mixer (FM-75 type, manufactured by Nippon Coke Industry Co., Ltd.), followed by screening with a mesh sieve with an opening of 150 μm, thereby obtaining a toner (T-1). Table 9 shows the physical properties of the obtained toner (T-1).

[0428] The following evaluations were performed using the obtained toner.

[0429] test

[0430] In consideration of the future high-speed printer, HP LaserJet Enterprise M609dn modified to have a processing speed of 450 mm / sec was used. Table 10 shows the evaluation results.

[0431] Low temperature fixability 1: Friction concentration reduction rate

[0432] The friction density reduction rate was measured using an external fixing device obtained by taking out the fixing device of the above evaluation machine, enabling the temperature of the fixing device to be arbitrarily set, and modifying so that the process speed was 450 mm / sec.

[0433] The above-mentioned apparatus was used in a low temperature and low humidity environment (temperature 15° C., humidity 10% RH) so that the toner load per unit area was set to 0.5 mg / cm 2 The unfixed image is passed through a fixing device set at 200° C. "PB PAPER" (manufactured by Canon Marketing Japan Co., Ltd., basis weight 66 g / cm 2 , letter paper) was used as evaluation paper. The obtained fixed image was washed with a 4.9 kPa (50 g / cm 2 ) was rubbed with a sillbon paper with a load of 1000 μm and evaluated by the decrease rate (%) of the image density before and after rubbing. The image density was measured by using an SPI filter with a Macbeth densitometer (manufactured by Macbeth Co.) as a reflection densitometer. Grades A and B were considered satisfactory.

[0434] A: The decrease rate of image density is less than 10.0%.

[0435] B: The decrease rate of image density is 10.0% or more and less than 15.0%.

[0436] C: The decrease rate of image density is 15.0% or more and less than 20.0%.

[0437] D: The decrease rate of image density is 20.0% or more.

[0438] Low temperature fixability 2: Missing Fixing Points

[0439] The missing fixing dots were evaluated using an external fixing device obtained by taking out the fixing device of the above evaluation machine, enabling the temperature of the fixing device to be arbitrarily set, and modifying so that the process speed was 480 mm / sec.

[0440] The above-mentioned apparatus was used to set the toner load per unit area to 1.0 mg / cm in a low temperature and low humidity environment (temperature 15° C., humidity 10% RH). 2 The unfixed full-surface solid image was passed through a fixing device set at 200° C. “PB PAPER” (manufactured by Canon Marketing Japan Co., Ltd., basis weight 66 g / cm 2 , letter paper) is used as evaluation paper.

[0441] By visually confirming the obtained image, the number of locations where toner was missing due to insufficient toner fixing was counted, and the missing fixing points were evaluated according to the following criteria: Ranks A and B were considered satisfactory.

[0442] A: The number of missing points is less than 3.

[0443] B: The number of missing points is 3 or more and less than 6.

[0444] C: The number of missing points is 6 or more and less than 9.

[0445] D: The number of missing points is 9 or more.

[0446] Uneven solid image density

[0447] The solid image density unevenness was evaluated using an external fixing device obtained by taking out the fixing device of the above evaluation machine, enabling the temperature of the fixing device to be arbitrarily set, and modifying it so that the processing speed is 480 mm / sec. In a high temperature and high humidity environment (temperature 32.5°C, humidity 85% RH), the toner load per unit area was set to 1.0 mg / cm 2 The unfixed full-surface solid image was passed through a fixing device set at 200°C.

[0448] Vitality type recording medium (manufactured by Xerox, basis weight 75 g / cm2) having Sa (arithmetic mean height) of 3.00 μm or more in the following surface roughness measurement 2 , letter paper) is used as evaluation paper for evaluation.

[0449] The density of the obtained image was measured randomly at 20 points, and the difference between the maximum and minimum values ​​of the measured density was evaluated. The image density was evaluated according to the following benchmark by changing the measurement spot diameter of a Macbeth densitometer (manufactured by Macbeth Co.) as a reflection densitometer to 3 mm and using an SPI filter. Grades A and B were considered satisfactory.

[0450] A: The concentration difference is less than 0.10.

[0451] B: The density difference is 0.10 or more and less than 0.20.

[0452] C: The density difference is 0.20 or more and less than 0.30.

[0453] D: The concentration difference is 0.30 or more.

[0454] Fogging reviews

[0455] The operation of outputting images with a print rate of 1% was repeated in a high temperature and high humidity environment (temperature 32°C, relative humidity 80%), and once the number of outputs reached 500, the system was left overnight. After that, the process of outputting 500 sheets and leaving them overnight as described above was repeated, and finally, 5,000 images were output and evaluated by the following method. "PB PAPER" (manufactured by Canon Marketing Japan Co., Ltd., basis weight 66 g / cm 2 , letter paper) is used as evaluation paper.

[0456] In the above-mentioned image output test, one image with a white background is output at a time. Then, for all images with a white background portion, the fog density (%) is calculated by the difference between the whiteness (reflectivity Ds (%)) of the white background portion of the image with a white background portion and the whiteness (average reflectivity Dr (%)) of the transfer paper (=Dr (%)-Ds (%)). The whiteness is measured by "REFLECTMETER MODEL TC-6DS" (manufactured by Tokyo Denshoku Co., Ltd.). An amber filter is used as a filter. For the print with the worst fog density, the following grade division is performed. Grades A to C are considered satisfactory.

[0457] A: The fogging concentration is less than 2.5%.

[0458] B: The fogging concentration is 2.5% or more and less than 4.5%.

[0459] C: The fogging concentration is 4.5% or more and less than 6.5%.

[0460] D: The fogging concentration is 6.5% or more.

[0461] Image density after durability test

[0462] The evaluation was conducted using the modified machine described above. The toner in the cartridge was emptied, and then the cartridge was filled with 700 g of the toner (T-1).

[0463] In a mode in which the machine is set to temporarily stop between jobs and then start the next job, a test was conducted in which 25,000 sheets were output using 2 prints / 1 job of a horizontal line pattern with a print rate of 1.5%. The evaluation was conducted in a high temperature, high humidity environment (temperature = 32.5°C, humidity = 85% RH). PB PAPER (Canon Marketing Japan Inc., unit area weight = 66 g / cm 2 , letter paper) is used for evaluation paper.

[0464] On the 25001th print, with a leading edge margin of 5 mm and a left and right side margin of 5 mm, an inspection image with a total of nine solid black small block images of 5 mm×5 mm is output at 3 positions, i.e., the left side, the right side and the middle, and at 3 positions at intervals of 30 mm along the length direction.

[0465] Image density was measured at nine solid black small block image areas of the inspection image and averaged. Image density was measured using a MacBeth densitometer (GretagMacbeth GmbH) as a reflection densitometer, using an SPI filter, and evaluated using the following benchmarks. Grades A and B were considered satisfactory.

[0466] A: The image density is 1.30 or more.

[0467] B: The image density is 1.10 or more and less than 1.30.

[0468] C: The image density is 0.90 or more and less than 1.10.

[0469] D: The image density is less than 0.90.

[0470] Storage under harsh conditions

[0471] The toner in the box was emptied and then filled with 700 g of toner (T-1). First, the toner was brought into a compacted filling state by knocking 300 times with the drive side facing downward. Then, a strict evaluation of the storability was performed under severe conditions by keeping the box in a severe environment (temperature = 40°C, humidity = 95% RH) for 90 days with the drive side facing downward.

[0472] Subsequently, the cartridge was taken out, and image output was performed in a high-temperature, high-humidity environment (temperature = 32.5° C., humidity = 85% RH) using the above-described modified machine and storability under severe conditions was evaluated.

[0473] For the image output test, first a test was conducted in which 20,000 prints were output using 2 prints / 1 job of a horizontal line pattern with a print rate of 2.0% in a mode in which the machine was set to temporarily stop between jobs and then start the next job. Then a check image was output under the same environment.

[0474] For the inspection image, a halftone image of 200 mm×280 mm (dot printing rate=23%) was output and the presence or absence of generation of vertical streaks in the inspection image was visually inspected and evaluated based on the following criteria: Ranks A and B were considered satisfactory.

[0475] A: No streaks are generated.

[0476] B: 1 to 5 streaks smaller than 1 mm were generated, and no streak larger than 1 mm was generated.

[0477] C: Six or more streaks smaller than 1 mm were generated, and no streak larger than 1 mm was generated.

[0478] D: Streaks of 1 mm or more occur.

[0479] Examples 2 to 18

[0480] Toners (T-2) to (T-18) were obtained in the same manner as in Example 1, except that the formulation shown in Table 10 was used. Table 9 shows the physical properties.

[0481] In addition, Table 11 shows the results of evaluation performed in the same manner as in Example 1.

[0482] Comparative Examples 1 and 2

[0483] Toners (T-19) to (T-20) were obtained in the same manner as in Example 1, except that the formulation shown in Table 10 was used. Table 9 shows the physical properties.

[0484] In addition, Table 11 shows the results of evaluation performed in the same manner as in Example 1.

[0485] Comparative Examples 3 and 6

[0486] Toners (T-21) and (T-24) were obtained in the same manner as in Example 1, except that the formulation shown in Table 10 was changed and the annealing treatment was not performed. Table 9 shows the physical properties.

[0487] In addition, Table 11 shows the results of evaluation performed in the same manner as in Example 1.

[0488] Comparative Example 4

[0489] (Preparation of Crystalline Polyester Resin Dispersion)

[0490] A total of 100 g of crystalline polyester (C-9) and 400 g of ethyl acetate were placed in a 2 L metal container, heated and dissolved at 75°C, and then rapidly cooled in an ice water bath at a rate of 27°C / min. Thereto, 500 ml of glass beads (3 mmφ) were added, and pulverization was performed for 10 hours with a batch sand mill device (manufactured by Kanpe Hapio Co., Ltd.), thereby obtaining "crystalline polyester-dispersion liquid 1".

[0491] Synthesis of non-crystalline polyester (low molecular weight non-crystalline polyester) resin

[0492] A total of 229 parts of ethylene oxide (2 mol) adduct of bisphenol A, 529 parts of propylene oxide (3 mol) adduct of bisphenol A, 100 parts of isophthalic acid, 108 parts of terephthalic acid, 46 parts of adipic acid and 2 parts of dibutyltin oxide were placed in a 5-liter four-necked flask equipped with a nitrogen introduction tube, a dehydration tube, a stirrer and a thermocouple. These components were reacted at 230° C. under normal pressure for 10 hours and further reacted under a reduced pressure of 10 to 15 mmHg for 5 hours, and then 30 parts of trimellitic anhydride were placed in a reaction container and reacted at 180° C. under normal pressure for 3 hours, thereby obtaining "non-crystalline polyester 1".

[0493] The number average molecular weight of "non-crystalline polyester 1" was 1800, the weight average molecular weight was 5500, the Tg was 50°C and the acid value was 20 mgKOH / g.

[0494] Synthesis of polyester prepolymer (binder resin precursor)

[0495] A total of 682 parts of ethylene oxide (2 mol) adduct of bisphenol A, 81 parts of propylene oxide (2 mol) adduct of bisphenol A, 283 parts of terephthalic acid, 22 parts of trimellitic anhydride and 2 parts of dibutyltin oxide were placed in a reaction vessel equipped with a cooling tube, a stirrer and a nitrogen introduction tube. These components were reacted at 230° C. under normal pressure for 8 hours and further reacted under a reduced pressure of 10 mmHg to 15 mmHg for 5 hours to obtain "Intermediate Polyester 1".

[0496] The number average molecular weight of "intermediate polyester 1" was 2100, the weight average molecular weight was 9500, the Tg was 55°C, the acid value was 0.5 mgKOH / g, and the hydroxyl value was 51 mgKOH / g.

[0497] Next, 410 parts of "intermediate polyester 1", 89 parts of isophorone diisocyanate and 500 parts of ethyl acetate were placed in a reaction vessel equipped with a cooling tube, a stirrer and a nitrogen introduction tube, and these components were reacted at 100° C. for 5 hours to obtain "prepolymer 1". The amount of free isocyanate in "prepolymer 1" was 1.53% by mass.

[0498] Synthesis of Ketimine

[0499] A total of 170 parts of isophoronediamine and 75 parts of methyl ethyl ketone were charged into a reaction container in which a stirring rod and a thermometer were set, and a reaction was performed at 50° C. for 5 hours, thereby obtaining “ketimine compound 1”.

[0500] The amine value of "ketimine compound 1" is 418 mgKOH / g.

[0501] Synthesis of Masterbatch (MB)

[0502] A total of 1200 parts of water, 1200 parts of magnetic particles 1 and 1200 parts of non-crystalline polyester resin 1 were added and mixed with a Henschel mixer (manufactured by Mitsui Mining Co., Ltd.), and the mixture was kneaded at 150° C. for 30 minutes using a double roll mill, then rolled and cooled, and pulverized with a pulverizer to obtain “master batch 1”.

[0503] Preparation of oil phase

[0504] A total of 378 parts of "non-crystalline polyester 1", 110 parts of carnauba wax, 22 parts of CCA (salicylic acid metal complex E-84: Orient Chemical Industries Co., Ltd.), and 947 parts of ethyl acetate were charged into a container in which a stirring rod and a thermometer were set, and the temperature was raised to 80° C. under stirring, the temperature was maintained at 80° C. for 5 hours, and then cooled to 30° C. within 1 hour. Next, 690 parts of "master batch 1" and 500 parts of ethyl acetate were charged into the container and mixed for 1 hour to obtain "raw material solution 1".

[0505] A total of 1324 parts of "raw material solution 1" were transferred to a container, and magnetic particles 1 and wax (WAX) were dispersed under three-pass conditions using a bead mill (ULTRA VISCO MILL, manufactured by AIMEX Co., Ltd.) at a liquid supply rate of 1 kg / hour, a circumferential speed of a disk of 6 m / sec, and a 0.5 mm zirconia bead filling rate of 80% by volume. Next, 1042.3 parts of a 65% ethyl acetate solution of "non-crystalline polyester 1" were added, and the mixture was passed through the bead mill once under the above conditions to obtain "pigment / WAX-dispersion liquid 1". The solid content concentration (130° C., 30 minutes) of "pigment / WAX-dispersion liquid 1" was 50%.

[0506] Synthesis of Organic Fine Particle Emulsion

[0507] A total of 683 parts of water, sodium salt of sulfuric acid ester of acidic ethylene oxide adduct of methacrylic acid (ELEMINOLRS-30: manufactured by Sanyo Chemical Industries, Ltd.) 11 parts, 138 parts of styrene, 138 parts of methacrylic acid and 1 part of ammonium persulfate were charged into a reaction vessel in which a stirring rod and a thermometer were set, and stirred at 400 rpm for 15 minutes to obtain a white emulsion. The temperature in the system was raised to 75° C. by heating, and the reaction was carried out for 5 hours.

[0508] Furthermore, 30 parts of a 1% aqueous solution of ammonium persulfate was added, followed by aging at 75°C for 5 hours to obtain an aqueous dispersion of a vinyl resin (a copolymer of styrene and a sodium salt of a sulfate ester of methacrylic acid and an ethylene oxide adduct of methacrylic acid) "fine particles-dispersion liquid 1". The volume average particle diameter of "fine particles-dispersion liquid 1" measured by LA-920 was 0.14 μm. A portion of "fine particles-dispersion liquid 1" was dried to separate the resin component.

[0509] Preparation of aqueous phase

[0510] A total of 990 parts of water, 83 parts of "fine particles-dispersion liquid 1", 37 parts of a 48.5% aqueous solution of sodium dodecyl diphenyl ether disulfonate (ELEMINOL MON-7: manufactured by Sanyo Chemical Industries, Ltd.), and 90 parts of ethyl acetate were mixed and stirred to obtain a milky white liquid. This liquid was designated as "aqueous phase 1".

[0511] Emulsification / desolventization

[0512] A total of 664 parts of "pigment / WAX-dispersion liquid 1", 109.4 parts of "prepolymer 1", 73.9 parts of "crystalline polyester-dispersion liquid 1", and 4.6 parts of "ketimine compound 1" were put into a container and mixed at 5000 rpm for 1 minute with a TK homomixer (manufactured by Tokushu Kika Kogyo Co., Ltd.). Then, 1200 parts of "aqueous phase 1" were added to the container, and mixing was performed at a rotation speed of 13,000 rpm for 20 minutes with the TK homomixer to obtain "emulsified slurry 1".

[0513] The "emulsified slurry 1" was put into a container equipped with a stirrer and a thermometer, desolventized at 30°C for 8 hours, and then matured at 45°C for 4 hours, thereby obtaining a "dispersed slurry 1".

[0514] Washing / Drying

[0515] After 100 parts of the "dispersed slurry 1" were vacuum filtered, the following operations (1) to (4) were performed twice to obtain a "filter cake 1":

[0516] (1) 100 parts of ion-exchanged water was added to the filter cake, followed by mixing with a TK homomixer (rotation speed 12,000 rpm, 10 minutes), and then filtered;

[0517] (2) 100 parts of a 10% sodium hydroxide aqueous solution was added to the filter cake of (1), followed by mixing with a TK homomixer (rotation speed 12,000 rpm, 30 minutes), and then vacuum filtration;

[0518] (3) 100 parts of 10% hydrochloric acid were added to the filter cake of (2), followed by mixing with a TK homomixer (rotation speed 12,000 rpm, 10 minutes), and then filtrated.

[0519] (4) 300 parts of ion-exchanged water were added to the filter cake of (3), followed by mixing with a TK homomixer (rotation speed 12,000 rpm, 10 minutes), and then filtered.

[0520] The “filter cake 1” was dried at 45° C. for 48 hours by a circulating air dryer, and toner particles were obtained by screening with a mesh having an opening of 75 μm.

[0521] 1.0 part in total of hydrophobic silica fine particles 1 (BET specific surface area 150 m 2 / g, hydrophobized with 30 parts of hexamethyldisilazane (HMDS) and 10 parts of dimethyl silicone oil relative to 100 parts of silica fine particles] was externally added to 100 parts of toner particles and mixed with a Henschel mixer (FM-75 type, manufactured by Nippon Coke Industry Co., Ltd.), and sieved with a mesh sieve with an opening of 150 μm to obtain a toner (T-22). Table 9 shows the physical properties.

[0522] Comparative Example 5

[0523] Synthesis of nonlinear non-crystalline polyester

[0524] 3-Methyl-1,5-pentanediol, adipic acid and trimethylolpropane were placed in a reaction vessel equipped with a cooling tube, a stirrer and a nitrogen inlet tube to obtain a molar ratio of hydroxyl group to carboxyl group [OH] / [COOH] of 1.1. At this time, tetraisopropoxytitanium was added at 1000 ppm relative to the total monomers to obtain 1.5 mol% of trimethylolpropane relative to the total monomers.

[0525] Next, the temperature was raised to 200°C in about 4 hours, then to 230°C in 2 hours, and the reaction was continued until the outflowing water disappeared. In addition, the reaction was carried out under a reduced pressure of 10 to 15 mmHg for 5 hours to obtain a non-linear non-crystalline polyester having a hydroxyl group.

[0526] Synthesis of Linear Non-Crystallinous Polyester

[0527] Ethylene oxide (2 mol) adduct of bisphenol A, propylene oxide (2 mol) adduct of bisphenol A, isophthalic acid and adipic acid are placed in a reaction vessel equipped with a nitrogen inlet tube, a dehydration tube, a stirrer and a thermocouple to obtain a molar ratio of hydroxyl group to carboxyl group [OH] / [COOH] of 1.2.

[0528] At this time, the diol consisted of 80 mol% of ethylene oxide (2 mol) adduct of bisphenol A and 20 mol% of propylene oxide (2 mol) adduct of bisphenol A, and the dicarboxylic acid consisted of 80 mol% of isophthalic acid and 20 mol% of adipic acid, and tetraisopropoxytitanium was added in an amount of 500 ppm based on the total monomers.

[0529] Next, these components were reacted at 230°C for 8 hours, and then reacted under a reduced pressure of 10 to 15 mmHg for 4 hours. Furthermore, trimellitic anhydride was added to obtain 1 mol% relative to the total monomers, and then reacted at 180°C for 3 hours, thereby obtaining a linear non-crystalline polyester. The weight average molecular weight was 5500 and the glass transition point was 50°C.

[0530] Preparation of masterbatch

[0531] A total of 1200 parts of water, 500 parts of carbon black Printex 35 (manufactured by Degussa Corp.) having a DBP oil absorption of 42 mL / 100 mg and a pH of 9.5, and 500 parts of a linear non-crystalline polyester were mixed using a Henschel mixer (manufactured by Mitsui Mining Co., Ltd.), and then kneaded for 30 minutes at 150° C. by using a two-roll mill. Next, after rolling and cooling, the mixture was pulverized using a pulverizer to obtain a masterbatch.

[0532] Preparation of release agent dispersion

[0533] A total of 50 parts of paraffin HNP-9 (manufactured by Nippon Seiro Co., Ltd.) having a melting point of 75° C. and 450 parts of ethyl acetate were placed in a container provided with a stirring rod and a thermometer, and the temperature was raised to 80° C. and maintained for 5 hours under stirring. Next, after cooling to 30° C. for 1 hour, dispersion was performed using a bead mill ULTRA VISCO MILL (manufactured by AIMEX Co., Ltd.) at a liquid supply rate of 1 kg / h, a circumferential speed of a disk of 6 m / sec, and a filling rate of 80% by volume under the conditions of three passes of zirconia beads having a diameter of 0.5 mm, thereby obtaining a release agent-dispersion liquid.

[0534] Preparation of crystalline polyester dispersion

[0535] A total of 50 parts of crystalline polyester (C-10) and 450 parts of ethyl acetate were placed in a container provided with a stirring rod and a thermometer, and the temperature was raised to 80° C. and maintained for 5 hours under stirring. Next, after cooling to 30° C. for 1 hour, dispersion was performed using a bead mill ULTRA VISCO MILL (manufactured by AIMEX Co., Ltd.) at a liquid supply rate of 1 kg / h, a circumferential speed of a disk of 6 m / sec, and a filling rate of 80% by volume under the conditions of three passes of zirconium oxide beads having a diameter of 0.5 mm, thereby obtaining a crystalline polyester-dispersion liquid.

[0536] Preparation of oil phase

[0537] A total of 50 parts of a release agent-dispersion liquid, 200 parts of a non-linear non-crystalline polyester, 500 parts of a crystalline polyester-dispersion liquid, 700 parts of a linear non-crystalline polyester, 50 parts of a masterbatch, and 2 parts of a ketimine compound 1 were put into a container and then mixed at 5000 rpm for 60 minutes using a TK homomixer (manufactured by Tokushu Kika Kogyo Co., Ltd.) to obtain an oil phase.

[0538] Preparation of aqueous dispersion of vinyl resin

[0539] A total of 683 parts of water, 11 parts of sodium salt of sulfuric acid ester of ethylene oxide adduct of methacrylic acid (ELEMINOLRS-30: manufactured by Sanyo Chemical Industries, Ltd.), 138 parts of styrene, 138 parts of methacrylic acid and 1 part of ammonium persulfate were charged into a reaction tank provided with a stirring rod and a thermometer, followed by stirring at 400 rpm for 15 minutes. Next, the temperature was raised to 75° C., the reaction was performed for 5 hours, and then 30 parts of a 1% by mass ammonium persulfate aqueous solution was added and ripening was performed at 75° C. for 5 hours, thereby obtaining an aqueous dispersion of a vinyl resin.

[0540] The volume average particle diameter of the aqueous dispersion of the vinyl resin measured by a laser diffraction / scattering particle size distribution measuring device LA-920 (manufactured by HORIBA) was 0.14 μm.

[0541] Preparation of aqueous phase

[0542] A total of 990 parts of water, 83 parts of the aqueous dispersion of the vinyl resin, 37 parts of a 48.5 mass % aqueous solution of sodium dodecyl diphenyl ether disulfonate (ELEMINOL MON-7: manufactured by Sanyo Chemical Industries, Ltd.), and 90 parts of ethyl acetate were mixed and stirred to obtain an aqueous phase.

[0543] Emulsification / desolventization

[0544] A total of 1200 parts of the aqueous phase was added to a container containing 1052 parts of the oil phase, and these components were mixed at 13,000 rpm for 20 minutes using a TK Homomixer (manufactured by Tokushu Kika Kogyo Co., Ltd.) to obtain an emulsified slurry.

[0545] The emulsified slurry was put into a container equipped with a stirrer and a thermometer, desolventized at 30°C for 8 hours, and then matured at 45°C for 4 hours, thereby obtaining a dispersed slurry.

[0546] Washing / Drying

[0547] A total of 100 parts of the dispersed slurry were vacuum filtered. The obtained filter cake was subjected to the following operations (1) to (4) twice:

[0548] (1) 100 parts of ion-exchanged water was added to the filter cake, followed by mixing with a TK Homomixer (manufactured by Tokushu Kika Kogyo Co., Ltd.) at a rotation speed of 12,000 rpm for 10 minutes, and then filtered;

[0549] (2) 100 parts of a 10% by mass sodium hydroxide aqueous solution was added to the filter cake of (1), followed by mixing with a TK Homomixer (manufactured by Tokushu Kika Kogyo Co., Ltd.) at a rotation speed of 12,000 rpm for 30 minutes, and then vacuum filtered;

[0550] (3) 100 parts of 10% by mass hydrochloric acid were added to the filter cake of (2), followed by mixing with a TK Homomixer (manufactured by Tokushu Kika Kogyo Co., Ltd.) at a rotation speed of 12,000 rpm for 10 minutes, and then filtered.

[0551] (4) 300 parts of ion-exchanged water were added to the filter cake of (3), followed by mixing with a TK Homomixer (manufactured by Tokushu Kika Kogyo Co., Ltd.) at a rotation speed of 12,000 rpm for 10 minutes, and then filtered.

[0552] The obtained filter cake was dried at 45° C. for 48 hours by a circulating air dryer, and base toner particles were obtained by sieving with a mesh having an opening of 75 μm.

[0553] 100 parts of base toner particles and 1.0 part of hydrophobic silica HDK-2000 (manufactured by Wacker Chemie AG) were mixed with a Henschel mixer (manufactured by Mitsui Mining Co., Ltd.) at a peripheral speed of 30 m / s for 30 seconds, and then the mixture was allowed to stand for 1 minute. The operation was repeated five times, and then the mixture was sieved with a mesh having an opening of 35 μm to obtain a toner (T-23). ​​Table 9 shows the physical properties.

[0554] [Table 9]

[0555]

[0556] In the table, (dG') / (dT)LM represents the minimum value of (dG') / (dT), α represents ethyl acetate insoluble matter α (mass %), β represents THF insoluble matter β (mass %), X represents cold crystallization peak X, and Y represents endothermic peak Y.

[0557] [Table 10]

[0558]

[0559] [Table 11]

[0560]

[0561] In the table, "CE" means "Comparative Example".

[0562] While the present invention has been described with reference to exemplary embodiments, it is to be understood that the invention is not limited to the disclosed exemplary embodiments. The scope of the claims is to be accorded the broadest interpretation so as to encompass all such modifications and equivalent structures and functions.

Claims

1. A toner comprising toner particles containing a binder resin and a crystalline polyester, characterized in that: The binder resin comprises a hybrid resin having a vinyl polymer part and a non-crystalline polyester part, The crystalline polyester is a polycondensation product of an alcohol component containing an aliphatic diol and an acid component containing an aliphatic dicarboxylic acid, and has at least one of a structure in which an aliphatic monocarboxylic acid is condensed at a terminal and a structure in which an aliphatic monoalcohol is condensed at a terminal, In the temperature T-storage elastic modulus G' curve obtained by measuring the toner at a temperature increase rate of 2.0°C / min using a flat plate rotational rheometer, (i) Storage elastic modulus G'(80℃) at 80℃ is 2.0×10 3 Pa to 2.0×10 5 Pa; and (ii) The minimum value of the change dG' / dT of the storage elastic modulus G' with respect to the temperature T in the range of 60°C to 80°C is -1.0×10 6 Below, and When the temperature of the toner is increased from 25°C to 120°C at a heating rate of 10°C / min, the projected area of ​​the toner at 80°C is S1 μm 2 , the radius of the projected area of ​​the toner at 80°C is R1 μm, and the radius of the projected area of ​​the toner at 120°C is S2 μm 2 hour, The S1, R1 and S2 satisfy the following formula (1): (1)S2 / S1×1 / R1≤0.

22.

2. The toner according to claim 1, wherein in the temperature T-storage elastic modulus G' curve, The storage elastic modulus G'(120℃) at 120℃ is 2.0×10 3 Pa to 2.0×10 4 Pa.

3. The toner according to claim 1 or 2, wherein the toner contains tetrahydrofuran-insoluble matter when the toner is extracted for 18 hours by Soxhlet extraction using tetrahydrofuran, and The storage elastic modulus G'(120°C) of the tetrahydrofuran insoluble material at 120°C measured by a flat plate rotational rheometer at a heating rate of 2.0°C / min was 1.0×10 5 Pa to 1.0×10 7 Pa.

4. The toner according to claim 1 or 2, wherein The amount of ethyl acetate-insoluble matter of the toner when the toner is extracted by Soxhlet extraction with ethyl acetate for 18 hours is α% by mass, and In the case where the amount of tetrahydrofuran-insoluble matter of the toner is β mass % when the toner is extracted for 18 hours by Soxhlet extraction using tetrahydrofuran, The α and the β satisfy the following formulas (2) and (3): (2)5.0≤β≤30.0 (3)10.0≤(α-β)≤40.0。 5. The toner according to claim 1 or 2, wherein The vinyl polymer part has a polymerized structure of at least one selected from the group consisting of acrylates and methacrylates, and The total amount of the at least one polymerized structure selected from the group consisting of acrylates and methacrylates in the vinyl polymer portion is 50% to 98% by mass. 6 . The toner according to claim 1 , wherein an amount of the non-crystalline polyester site in the hybrid resin is 50% by mass to 98% by mass. 7 . The toner according to claim 1 , wherein the non-crystalline polyester moiety has a structure cross-linked by at least one selected from the group consisting of trivalent or higher polyols and trivalent or higher polycarboxylic acids.

8. The toner according to claim 1 or 2, wherein When the carbon number of the aliphatic diol is C1, and the carbon number of the aliphatic dicarboxylic acid is C2, the sum of C1 and C2 is 10 to 16.

9. The toner according to claim 1 or 2, wherein In the differential scanning calorimeter DSC measurement of the toner, when (i) the number of cold crystallization peaks in the range of 40°C to 120°C during cooling is X, and (ii) When the number of endothermic peaks in the range of 40°C to 120°C during the second heating is Y, X and Y satisfy the following equations (7) and (8): (7)X≥1 (8)Y≥X+1.

10. The toner according to claim 1 or 2, wherein The toner particles include a crystalline polyester resin, and In differential scanning calorimetry of the toner, The temperature was raised from 25°C to 120°C at a rate of 1000°C / sec. The temperature was maintained at 120°C for 100 milliseconds, then cooled to 25°C at a rate of 1000°C / sec, and then The temperature is raised to 120°C at a rate of 1000°C / sec, and When the glass transition temperature during the first heating is Tg1°C, and the glass transition temperature during the second heating is Tg2°C, Satisfies the following equations (9) and (10): (9) 65℃≤Tg1≤85℃ (10)7℃≤Tg1-Tg2≤30℃.

11. The toner according to claim 1 or 2, wherein In the temperature T-storage elastic modulus G' curve, the storage elastic modulus is 1.0×10 3 The temperature at Pa is T1℃, In a DSC curve obtained by differential scanning calorimetry of the toner, an endothermic peak exists in the range of 30° C. to 120° C., and When the peak temperature of the peak existing on the lowest temperature side of the endothermic peak is T2°C, Satisfies the following formula (11): (11)T1-T2≥40.

Citation Information

Patent Citations

  • Electrophotographic toner, two-component developer including the toner, and image forming apparatus

    JP2014167602A

  • toner

    US20160091813A1